Correction: Naringenin attenuates amiodarone-induced pulmonary fibrosis in rats via modulation of the SIRT1/NF-κB signalling pathway - Heba M. Arakeep; Wafaa Abdelaziz Emam; Amena Rezk Mohammed; Marwa H. Sedira; Marwa Mahmoud Awad; Alshimaa Aboalsoud; Rehab Ahmed Ahmed El-Shaer; Azza Mostafa Mohammed Aboshanady; Norhan Ahmed AbuoHashish (Molecular Biology Reports, 2026)

Naringenin attenuates amiodarone-induced pulmonary fibrosis in rats via modulation of the SIRT1/NF-κB signalling pathway - Heba M. Arakeep; Wafaa Abdelaziz Emam; Amena Rezk Mohammed; Marwa H Sedira; Marwa Mahmoud Awad; Alshimaa Aboalsoud; Rehab Ahmed Ahmed El-Shaer; Azza Mostafa Mohammed Aboshanady; Norhan Ahmed AbuoHashish (Molecular Biology Reports, 2026)

Comparative analysis of the thermal performance statement of a hybrid solar still combining preheating and active forced condensation - Muntadher Mohammed Ali Saeed; Hassanain Ghani Hameed; Saif Ali Kadhim; Hussein Awad Kurdi Saad; Karar Abdelkarim Yahya; Ali M. Ashour; Abdallah Bouabidi (Journal of Water Process Engineering, 2026)

Paleomagnetic calibration, mineralogy, provenance, and diagenetic controls on Upper Paleozoic siliciclastic successions: Implications for chronostratigraphy, basin evolution, and reservoir quality on the northern Gondwana margin - Haitham M. Ayyad; Mohamed W. Abd El-Moghny; Mohamed H. Helal; Ashraf M. Al-Nashar; Nabil A. Abdel Hafez; Ahmed Awad; Sherif Farouk; Mohamed Fathy (Journal of African Earth Sciences, 2026)

Development of Hydrocolloid-Structured Choline Chloride–Lactic Acid Eutectogels Enriched with Terminalia catappa Extract through Intermolecular Hydrogen Bonding for Active Fruit Coating and Postharvest Quality Preservation - Oscar Zannou; Nour M.H. Awad; Mansuri M. Tosif; Ayşegül Beşir Özgeçen; Gulden Goksen (Food Hydrocolloids, 2026)

Reciprocal adaptation is critical in enhancing S. aureus and P. aeruginosa biofilm biomass - Xiaohan Sun; Clare M. Cooksley; Muhammed Awad; Emma F. Barry; Alkis J. Psaltis; Peter-John Wormald; Sarah Vreugde (Archives of Microbiology, 2026)
Polymicrobial communities impose a great challenge for clinical management of chronic infections. It is a consensus now that microbes exist as aggregated colonies shielded within polymeric matrix. Within this matrix more than one bacterial species can exist either in symbiotic or rival relationships. Herein, we investigated the host-specific interspecies interactions between Staphylococcus aureus and Pseudomonas aeruginosa in chronic rhinosinusitis (CRS). The indirect interaction between the two species was assessed using Transwell co-culture chambers, where S. aureus and P. aeruginosa ( n = 3 each) derived from CRS patients were cultured in separate chambers that allowed exchange of soluble factors. Later the biofilm biomass of each species was evaluated and compared to single species biofilm. Further, the influence of the co-culture conditions on antibiotic tolerance was evaluated. When derived from the same patient, co-cultured bacteria increased the biofilm biomass of each other significantly by 3.0-4.9 fold ( p p

In Vitro and In Silico Investigations of the Acaricidal Activity of Carvacrol Against Rhipicephalus annulatus - Samar M. Ibrahium; Abdel-Azeem S. Abdel-Baki; Fatma I. Abo El-Ela; Aliaa A. Balegh; Ahmed A. Wahba; Saleh Al-Quraishy; Ezzat M. Awad; Manal Ahmed; Wafaa G. Mahmoud; Shawky M. Aboelhadid (Acta Parasitologica, 2026)

Synergistic cardioprotection by liraglutide and deferoxamine against doxorubicin-induced cardiotoxicity via modulation of ACSL-4/Nrf-2/GPX-4 signaling - Nada Monir; Omneya Galal; Azza S. Awad; Hala F. Zaki; Mona M. Saber (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Paclobutrazol-mediated improvement of brown spot resistance in rice seedlings under salinity stress conditions - Hossam S. El-Beltagi; Mohamed Fathi El-Nady; Adel A. Rezk; Abdelaziz M. Tahoon; Hosny Hamed Kesba; Elsayed Abd Elmaksoud Abomarzoka; Ahmed Mahmoud Ismail; Awad Mohamed El-Sayed; Wael Elmenofy; Metwaly Mahfouz Salem Metwaly (European Journal of Plant Pathology, 2026)

Endophytic fungi: A potential source of bioactive compounds - Sherien M.M. Atalla; Aliaa R El Shamy; Wesam M Hussein; Ruba A. Ashy; Rawabi Zahed; Hassan M Awad (South African Journal of Botany, 2026)

Enhancing tomato plant immune responses through microbial bio-inducers against Pythium irregular root rot - Mohamed S. Attia; Mohamed M. Nofel; Amer M. Abdelaziz; Eslam K. Kandil; Abdulrahman E. Singer; Youssef E. Madkour; Mohammed G. Awad; Muostafa M. Abdelsamad; Abdullah A. Mahmoud; Hassan A. Rudayni; Amr Elkelish; Gharieb S. El-Sayyad (Physiological and Molecular Plant Pathology, 2026)

Robust Spatio-temporal reconstruction of XCO₂ using OCO-2 and OCO-3 satellite observations and deep learning-based uncertainty quantification - Mohamad M. Awad; Saeid Homayouni (Next Research, 2026)

Mitigating effect of naringenin on potassium bromate-induced nephrotoxicity in vivo - Iftekhar Hassan; Hossam Ebaid; Badar ul Islam; Jameel Al-Tamimi; Zeinab Abdelftah; Shazia Aman; Ibrahim M. Alhazza; Ezzat M. Awad (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
The usage of potassium bromate (PB) in various consumer items and food and chemical industries poses a serious health risk like nephrotoxicity along with other toxic abuses. The compound elicits mild to severe toxic insults in a dose-dependent way in vivo and can even trigger carcinogenesis if exposed for long. This investigation ascertains the protective effect of naringenin (NIR), a polyphenol, in the PB-challenged rats. The animals were categorized into five treatment groups: Group I (control), and Groups II and III were treated with PB alone (100 mg/kg) and NIR alone (20 mg/kg), respectively. The groups– IV and V were administered with NIR at 20 and 40 mg/kg in the PB-exposed rats. The animals were killed to get their kidney and blood samples for biochemical, molecular, and histological alaysis. The group II exhibited an enhanced level of renal function and toxicity markers in serum, validating nephrotoxicity. Further, dysregulated redox parameters (GSH and MDA) and suppressed antioxidant enzymes (SOD and CAT) consolidated the same. Group III showed negligible toxicity, with most of the parameters' values close to the control. Intriguingly, groups- IV and V bestowed remarkable alleviation in the PB-induced nephrotoxicity in a dose -dependent way. In addition, the comet assay and histological evaluation further confirmed these findings. The study concludes that NIR effectively protects against PB-induced nephrotoxicity in rats attributed by regulating oxidative stress and promoting structural restoration at both macromolecular and cellular levels. Therefore, NIR is a suitable candidate for use in consumer products containing PB or as a treatment to alleviate nephrotoxicity caused by PB or similar compounds.

Comparative in vitro and in vivo acaricidal activity of D-limonene against Argas persicus with biochemical and ultrastructural insights - Asmaa A. Hassan; Shawky M. Aboelhadid; Asmaa A. Kamel; Waleed M. Arafa; Abdel-Azeem S. Abdel-Baki; Khaled M. Shokier; Saleh Al-Quraishy; Ezzat M. Awad; Shams G. Abd El-Kareem; Sahar M. Gadelhaq (Biocatalysis and Agricultural Biotechnology, 2026)

Photocatalytic Degradation of Oseltamivir Phosphate and Residual Toxicity Evaluation of its Metabolites as a Sustainable Solution for Antiviral Drug Pollution - Abd El-Nasser H. M. Muhanny; Hanem M. Awad; Nourhan Hassan; Mona S. Ragab; Ola R. Shehab (Water, Air, & Soil Pollution, 2026)
The global consumption of antiviral drugs (AVD) during the ongoing pandemic has overwhelmed wastewater treatment plants, which struggle to effectively remove these compounds due to their hydrophilic nature. Current methods fall short of fully degrading AVDs, leaving behind potentially harmful residues. In this study, we aim to investigate the photocatalytic degradation of oseltamivir phosphate under UV light, with and without the presence of catalysts. To address this challenge, we explored the use of titanium dioxide (TiO 2 ) as a cost-effective and highly stable photocatalyst. In combination with carbon nanotubes and UV-A radiation (365 nm), TiO 2 demonstrated exceptional efficiency in degrading oseltamivir phosphate, a common antiviral drug. Under optimized conditions, initial concentration (C0) of 1 mg/L, TiO 2 and carbon nanotube catalyst concentration (Ccat) of 0.1 g/L, and pH of 6.0, the system achieved complete degradation (100%). The degradation process followed pseudo-first-order kinetics with a strong correlation coefficient (r 2 = 0.8593). To confirm the degradation, we monitored changes in pH, Raman shifts, and FTIR spectra before and after treatment. Analytical methods, including UV–visible spectrophotometry and High-Performance Liquid Chromatography (HPLC), were used to quantify the degradation efficiency. Moreover, toxicity studies on wheat seeds indicated that the metabolites produced during oseltamivir phosphate degradation were non-toxic, suggesting the process is environmentally safe. This approach offers a promising solution for addressing AVD pollution in wastewater while minimizing ecological risks.

Genetic Diversity Analysis Using Start Codon Targeted (SCoT) and Sequence-Related Amplified Polymorphism (SRAP) Markers and Some Leaf Anatomical Traits in Sixteen Rutaceae Taxa - Mohamed A. Abdein; Samah O. Osman; Amr M. M. Mahmoud; Sahar A. M. Shamseldin; Mai M. Wahba; Sayed Y. Mohamed; Emadeldin A. H. Ahmed; Salwa El-Habashy; Rania A. E. Abdelzaher; Noha A. Sukar; Amany M. Mousa; Amal Ahmed Alyamani; et al. (Plant Molecular Biology Reporter, 2026)

Repellent interactions of DEET with essential oil components against the red flour beetle, Tribolium castaneum (Herbst) - Shawky M. Aboelhadid; Hassan M. Eltalawy; Saleh Al-Quraishy; Ezzat M. Awad; Manal Ahmed; Heba Abdeltwab; Samar M. Ibrahium; Abdel-Azeem S. Abdel-Baki (Journal of Plant Diseases and Protection, 2026)

Development and Evaluation of Econazole Nitrate Loaded Cubosomal Gel for Enhanced Topical Antifungal Therapy - Sonam M. Gandhi; Yakub Ismail Bhorat; Devesh U. Kapoor; Samaresh Pal Roy; Omar Awad Alsaidan; Sami I. Alzarea (Journal of Pharmaceutical Innovation, 2026)

Efficacy and safety of Ongericimab in patients with hypercholesterolemia: a systematic review and meta-analysis - Ahmed L. Youseif; Ahmed F Younis; Ziad W. Elmezayen; Mohamed Eldahrawy; Noha Hammad; Belal Mohamed Hamed; Amr Reda Saleh; Alaa Ashraf Mohamed; Omar Abdulrahman Saad; Aya M. Ramadan; Abdelaziz A. Awad (European Journal of Clinical Pharmacology, 2026)

Eco-friendly suppression of date palm (Phoenix dactylifera L.) Fusarium wilt using Streptomyces biocontrol agents from the rhizosphere - Mohamed A. Awad; Adel D. Al-Qurashi; Kamal A. M Abo-Elyousr (Journal of Plant Pathology, 2026)

Natural radioactivity distribution and environmental risk assessment of Upper Cretaceous-Lower Paleogene sedimentary successions of Wadi Queih area, Red Sea, Egypt - Alanoud A. Atia; Awad A. Omran; Ahmed R. M. El Younsy; Nageh A. Obaidalla; Abdelhamid M. Salman; Ghada Salaheldin (Environmental Monitoring and Assessment, 2026)

Empagliflozin as a potential therapy for PCOS: Restoring hormonal balance and ovarian function in a letrozole-induced rat model - Heba A. Habib; Mahmoud El-Daly; Yahya I. Asiri; Saud Alqahtani; Eman M. Awad; Sara MN. Abdel Hafez; Al-Shaimaa F. Ahmed; Aliaa F. Anter (Tissue and Cell, 2026)

Food spoilage and packaging solutions: key Mediterranean case studies - Maria Lucia Valeria de Chiara; Ines Essid; Olfa Daaloul; Hana Mallek; Valérie Guillard; Fanny Coffigniez; Mina Hariri; Sarah Lammi; Mia Kurek; Nour M.H. Awad; Asmaa M. Abushady; Adilson R. Locali-Pereira; et al. (Food Research International, 2026)

Bioactive-driven modulation of structural, rheological, and functional properties in tiger nut–based frozen food matrices enriched with selected fruit pulps - Hesham A. Ismail; Wafaa M. Salama; Arwa M. Ali; Wael F. Elkot; Tawfiq Alsulami; Suleiman A. Althawab; Basim M. Alohali; Ammar Al-Farga; Rezk A. Awad (Food Research International, 2026)

Development and Characterization of a Crisaborole-Loaded Niosomal Gel for Enhanced Topical Delivery in Atopic Dermatitis Management - Sonam M. Gandhi; Rajbhar Nandanam Ashok; Devesh U. Kapoor; Omar Awad Alsaidan (Journal of Pharmaceutical Innovation, 2026)

Modulation of arsenic uptake and detoxification in maize (Zea mays L.) by plant-based iron oxide nanoparticles - Tauseef Anwar; Huma Qureshi; Muhammad Imran; Hossam S. El-Beltagi; Salohiddinjon Yunusov; Shuqurillo Ziyadov; Muydinjon M. Muminov; Gamal Awad El-Shaboury; Dilbar Bazarbayeva; Ibtisam M. Alsudays; Khalid H. Alamer; Munisa Bekmukhamedova; et al. (Biodegradation, 2026)

Therapeutic Impact of Plant-Derived Extracts and their Silver Nanoparticle-Loaded Extracts on the Zoonotic Parasite Hymenolepis Nana Infection - Wesam M. A. Elgendy; Hany M. El-Wahsh; Doaa Naguib; Rasha A. Elmahy; Suzan Awad AbdelGhany Morsy; Ashraf Fawzy Mosa Ahmed; Marim Fayz Abdow; Nabeel Hussain Alhussainy; Faten Abdullah Al Braikan; Ahmed Bendari; Akram Abu-Okail; Amira Mohamed AbdelHady Elhosyni (Acta Parasitologica, 2026)

Effects of a Magnetic Field on Surface and Subsurface Drip Irrigation Water, Tomato Plants and Desert Sandy Soil Characteristics - Ahmed A. Al‐Othman; Doaa M. El‐Shinawy; Awad Ali Tayoush Oraiath; Abdallah Elshawadfy Elwakeel; Ahmed Z. Dewidar; Ahmed Elbeltagi; A. H. Hamza (Irrigation and Drainage, 2026)
This study, conducted in Shosha, Minia, Egypt, aimed to evaluate the effects of magnetically treated saline groundwater on both soil characteristics and the performance of tomato crops grown in arid sandy soils. The influence of magnetic fields on water quality was first assessed to determine its suitability for irrigation. Subsequently, the combined effects of MWT with different irrigation methods—namely, surface drip irrigation (SDI) and subsurface drip irrigation (SSDI)—as well as system design types (closed vs. open systems), were examined to understand their impact on soil health and chemical properties under saline conditions. Magnetic treatment significantly improved water quality by reducing sodium and chloride accumulation in the root zone and decreasing the Na/Cl ratio from 1.07 to 0.98. This facilitated salt leaching and reduced plant salt stress. Treated water also lowered soil electrical conductivity (EC) and soluble ion concentrations while increasing soil moisture retention and field capacity. SSDI with magnetised water achieved a wetted soil volume of 94,500 cm 3 —vastly greater than 6720 cm 3 under unmagnetised open SDI. Emitter clogging ratio (ECR) was reduced from 12% to 5%, improving system reliability. Application efficiency rose from 89% to 97%, and emission uniformity improved from 90% to 96%.

Numerical analysis of flow characteristics through stilling basin at pump stations outlets - E. M. Elshahat; M. Elhousseiny; M. R. Fahmy; H. F. Abd-Elhamid; M. Zeleňáková; M. Awad (International Journal of Energy and Water Resources, 2026)

Isolation, Identification, and Pathogenicity of Entomopathogenic Fungal Strains and Their Secondary Metabolites Against Spodoptera frugiperda (Lepidoptera: Noctuidae) - Fatmaalzahraa A. Senousy; El Arnaouty S.A; Mona N. Kortam; Ismail M. Ismail; Mona Awad; Marwa A. Zayton (Neotropical Entomology, 2026)
The fall aِrmyworm, Spodoptera frugiperda (J.E. Smith), causes significant yield losses due to its high fecundity, broad host range, defoliation capability, and voracious larval feeding. Biological control using microorganisms has gained attention as a sustainable alternative to chemical pest management. Entomopathogenic fungi employ distinct modes of action and produce secondary metabolites with insecticidal properties. This study aimed to isolate and identify indigenous entomopathogenic fungal species and evaluate their pathogenicity against S. frugiperda . Three isolates belonging to the division Ascomycota were recovered from soil samples and identified as Botryotrichum domesticum isolate MP3H-5, Albifimbria verrucaria isolate E16, and Purpureocillium lilacinum isolate WARSO2 6 8. When applied at a concentration of 1 × 10 9 conidia mL⁻ 1 , the fungal isolates induced significant cumulative mortality (60 to 84.44%) in S. frugiperda larvae at 14 days post-treatment. Albifimbria verrucaria was the most virulent, exhibiting the lowest LC 50 (2 × 10 7 conidia mL⁻ 1 ) and LT 50 (0.46 days). At a lower concentration of 1 × 10 7 conidia mL⁻ 1 , the P. lilacinum isolate caused the highest pupal mortality (80%) at 7 days post-treatment. Crude fungal metabolites also demonstrated larvicidal activity, resulting in cumulative mortality rates of up to 50%. Furthermore, larvae treated with the entomopathogenic fungi showed elevated catalase activity. The high toxicity observed is likely associated with fungal secondary metabolites, which were characterized using GC-MS analysis. Under laboratory conditions, the tested entomopathogenic fungal isolates demonstrated strong potential as microbial agents for the control of S. frugiperda . However, further field-based validation is necessary to confirm their efficacy.

Lectin Gene Families in Three Phaseolus Species: Genome-Wide Identification, Evolutionary Analysis, Pleiotropic Effect, and Regulation Under Multiple Stress Conditions - Makarim Elfadil M. Osman; Amina I. Dirar; Mohanad A. Ibrahim; Rieham Sallah H. Osman; Doaa Awad Yassin Ali; Somia Elmosharaf Elrayah Yousif; Hana Badreldin Mohamed Abakar; Nada Hassan M. Haj; Emadeldin Hassan E. Konozy (Journal of Molecular Evolution, 2026)

Alteplase versus tenecteplase in acute ischemic stroke with large vessel occlusion: a systematic review and meta-analysis - Mostafa Hossam El Din Moawad; Ibrahim Serag; Ahmed A. Abo Elnaga; Dina Essam Abo-elnour; Hamza A. Abdul-Hafez; Mohamed Ahmed Hammad; Lobna Ahmed Mohamed; Rawan Kamal Mohamed; Amir N. Attia; Abdelaziz A. Awad; Ibraheem M. Alkhawaldeh; Mahmoud Hegazy; et al. (European Journal of Clinical Pharmacology, 2026)

Biochar and GA3-mediated enhancement of wheat performance under combined salinity and drought: physiological and biochemical insights for resilient agriculture - Tauseef Anwar; Huma Qureshi; Hossam S. El-Beltagi; Alisher Shokirov; Nargiza Khudoyberdiyeva; Akhtam Nurniyazov; Oybek Mamarakhimov; Nazih Y. Rebouh; Maryam M. Alomran; Ibtisam M. Alsudays; Khalid H. Alamer; Dilrabo Kodirova; et al. (Biodegradation, 2026)

A flexible photothermal device based on silver nanoparticle-integrated cellulose matrix for interfacial solar steam generation: Rethink waste and reinvigorate water - Mina Shawky Adly; Salma M. Abo Kamar; Mohamed Noufal; Soheir A. EL-Hakam; Awad I. Ahmed; Amr Awad Ibrahim (Desalination, 2026)

A state-of-the-art review of injury severity analysis in traffic crashes: toward a generalized modeling framework - Marwa Awad; Ghada S. Moussa; Amr M. Wahaballa; Hassan Younes (Innovative Infrastructure Solutions, 2026)
The modeling of injury severity (INJ-S) in road traffic crashes has evolved significantly with the advent of machine learning (ML) and hybrid data-driven approaches. This review provides a comprehensive synthesis of over 70 recent studies across diverse geographic regions and crash contexts, focusing on the integration of ML and advanced econometric techniques for predicting injury outcomes. The article examines a wide range of datasets, severity classifications, and methodological innovations, highlighting how ensemble methods, deep neural networks, and random parameter models enhance predictive performance and interpretability. It also emphasizes the critical role of spatial and temporal factors in shaping INJ-S, advocating for context-aware models that account for regional and time-based variability. Key findings highlight the persistent influence of behavioral, environmental, vehicular, and infrastructural factors on crash severity, as well as the increasing importance of preprocessing, feature engineering, and post-modeling interpretability tools, such as SHapley Additive exPlanations (SHAP) and global sensitivity analysis (GSA). A generalized analytical framework is proposed to guide future research, spanning data acquisition, model development, and policy-relevant interpretation. By bridging transportation engineering, data science, and public health perspectives, this study lays the foundation for scalable, interpretable, and geographically inclusive INJ-S modeling aimed at advancing global road safety.

Addressing global food challenges with microalgae: Green yogurt enriched with Spirulina platensis as a sustainable probiotic dairy product for improved health and nutrition - Nasser S. Flefil; Hanem Awad; Ahmed M. Abd El-Sabour; Asmaa Negm El-Dein (Food and Humanity, 2025)

Association of PD-1 immune checkpoint polymorphisms with oral cancer risk: results from a Pakistani case-control study - Iqra Mubeen; Arifa Shabbir; Ezzat M. Awad; Humaira Naeemi; Talin Barisani-Asenbauer; Muhammad Usman Rashid; Naila Malkani (Molecular Biology Reports, 2025)

miRNAs and their multifaceted role in cutaneous wound healing - Reda M. Mansour; Sherif S. Abdel Mageed; Farah A. Awad; Mohamed M. Sadek; Shehab Ahmed Adel; Alaa Ashraf; Khaled M. Alam-Eldein; Nada E. Ahmed; Rana Y. Abdelaziz; Esraa Farid Tolba; Hend H. Mohamed; Nehal I. Rizk; et al. (Functional & Integrative Genomics, 2025)

From fatty liver to fibrosis: the impact of miRNAs on NAFLD and NASH - Reda M. Mansour; Sherif S. Abdel Mageed; Ahmed I. Abulsoud; Ghadir A Sayed; Radwa H. Lutfy; Farah A. Awad; Mohamed M. Sadek; Abanoub A. S. Shaker; Osama A. Mohammed; Mustafa Ahmed Abdel-Reheim; Hanan Elimam; Ahmed S. Doghish (Functional & Integrative Genomics, 2025)

Combined efficacy of Bacillus amyloliquefaciens CIM95 and melatonin in reducing anthracnose in strawberries (Fragaria × ananassa Duch.) by enhancing antioxidant activity and defense-related genes - Anam Moosa; Arwa Abdulkreem AL-Huqail; Dikhnah Alshehri; Suliman Mohammed Suliman Alghanem; Faisal Zulfiqar; Gamal Awad El-Shaboury; Fahad Al-Asmari; Nurah M. Alzamel; Layla A. Alahmari; Tolga İzgü (International Journal of Food Microbiology, 2025)

A novel green μSPE platform based on magnetic Fe₃O₄-activated carbon and deep eutectic solvents for ultrasensitive determination of rhodamine B in aqueous and food matrices - Mona Moheb; Ahmad M. El-Wakil; Fathi S. Awad (Food Chemistry, 2025)

Fabrication of nanomagnetite/graphitic carbon nitride composite for adsorption and photo-Fenton decomposition of methylene blue dye - A. M. Awad; G. A. El-Naggar; A. F. Hassan (International Journal of Environmental Science and Technology, 2025)
Pollution caused by synthetic dyes is an urgent issue, necessitating the development of highly effective and environmentally friendly solid adsorbents and catalysts. Herien, nanomagnetite/graphitic carbon nitride composite (NgCN) was developed for the adsorption and photo-Fenton breakdown of methylene blue. The formed NgCN composite has low band gap energy (2.14 eV), high surface area of 94.9 m 2 /g, various chemical surface functional groups, and a TEM average particle size of 10 nm. The adsorption and Fenton approach were studied under several application circumstances. The Langmuir maximum adsorption capacity was verified by NgCN (80.65 mg/g) at pH = 6, and the adsorption was well-applied by Langmuir, Temkin, and Freundlich, as adsorption isotherm models. The kinetic experiments proved the application of nonlinear PSO and Elovich models, and 6 h is the optimum adsorption equilibrium time. The degradation data from Fenton and photo-Fenton show that NgCN is more effective than nanomagnetite (Ng) and graphitic carbon nitride ( g -C 3 N 4 ). Methylene blue breakdown exhibits 100% using NgCN catalyst under UV light at 40 °C, at 40 min of the catalytic activity. Kinetic and thermodynamics of MB decomposition by photo-Fenton verified the PFO, nonspontaneous, and endothermic catalytic procedure. Throughout eight photo-Fenton cycles, the reusability of NgCN declined by only 4.0%. The NgCN demonstrated significant dye adsorption and decomposition efficacy at varying pollutant concentrations. The fabricated material is a promising solid adsorbent as well as a photo-Fenton catalyst for the removal of organic pollutants.

A novel mechanistic study on inhibiting influenza A virus replication by a newly extracted polypeptide targeting host autophagy - Nedaa Alalem; Mai Alalem; Ahmed Awad; Amany M. Elshamy; Osama R. Elalem; Ahmed M. Tabl; Mohamed E. Ebaid; Hany Khalil (Archives of Microbiology, 2025)

Ameliorative effects of hesperidin against cyclophosphamide-induced ovarian dysfunction in the female rat model - Abdelmonem Awad Hegazy; Eman Ramadan Abd El Fattah; Marwa Mohamed Mahmoud Abdelfattah; Marwa M. Ahmad; Dalia Ibrahim Ahmed Mesallam; Samaa Salah Abd El-Fatah (Tissue and Cell, 2025)

Daxas provides renoprotective effects in ischemia-reperfusion injury by targeting apoptosis, oxidative stress, and inflammation pathways - Nashwa Barakat; Karima Elsharkawy; Aml Awad; Salma M. Khirallah (Tissue and Cell, 2025)

Impact of phytocannabinoids THC, CBD and their acidic counterparts THCA and CBDA on TGF-β1-induced epithelial- mesenchymal transition in human conjunctival epithelial cells - Anil Baskan; Ezzat M. Awad; Ava Elahi; Javeria Pervaiz; Talin Barisani-Asenbauer (Phytochemistry Letters, 2025)

Sustainable bi-layer membrane for efficient interfacial solar steam generation: Silver‑carbon core-shell nanoparticles for enhanced light absorption and stability - Salma M. Abo Kamar; Amr Awad Ibrahim; Soheir A. EL-Hakam; E.A. El-Sharkawy; Awad I. Ahmed; Mina Shawky Adly (Desalination, 2025)

Xanthan gum-based formulations for additive manufacturing: Scientific developments in drug delivery and biomedical applications - Riya Patel; Mansuri M. Tosif; Omar Awad Alsaidan; Bhupendra Prajapati (Carbohydrate Polymers, 2025)

Pioglitazone mitigates acetic acid-induced colitis in rats via epigenetic-modulation and antioxidant mechanisms - Suzan Awad AbdelGhany Morsy; Lobna M. M. A. Abd El Mottelib; Sara Assem; M. M. Abd El Aziz; Anne H. Elgeziry (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Variability of Saharan cyclone tracks, II: synoptic study - Abdulhaleem H. Labban; Adel M. Awad (Meteorology and Atmospheric Physics, 2025)

Simvastatin loaded surface-decorated 3D-dendritic mesoporous silica nanoparticles for enhanced antihyperlipidemic activity: in vitro and in vivo appraisal - Abdulsalam M. Kassem; Elsaied H. Barakat; Maged K. Elsayad; Sherif E. Emam; Tarek M. Ibrahim; Ayman Salama; Mohammed Elmowafy; Nabil K. Alruwaili; Omar Awad Alsaidan; Mohamed A. Abdelgawad (Drug Delivery and Translational Research, 2025)

Multifaceted analysis of cymothoids parasitism, environmental stressors and heavy metal bioaccumulation dynamics in mediterranean farmed fish in Egypt - Mohamed A. Atwah; Mohsen A. Khormi; Awad A. Abdelbaky; Ola Hasan Abd El Megeed; Ali M. Aborasain; Mai A. Salem; Mohamed A. Soliman; Hanan S. Khalefa; Hanan H. Abd-El Hafeez; Mohamed Abdelsalam (Aquaculture International, 2025)
This study investigated the interactions between cymothoids parasitism, environmental stressors, and heavy metal bioaccumulation in commercially farmed fish in the Deeba Triangle area, Egypt. Over 600 fish, comprising gilthead seabream ( Sparus aurata ) and two mullet species ( Mugil cephalus and Liza ramada ), were examined during spring and summer 2023. Seasonal variations in cymothoids parasite infestation showed higher prevalence during spring ( S. aurata : 37%, mullets: 100%) compared to summer ( S. aurata : 20%, mullets: 80%). Morphological and molecular characterization identified the parasite as Livoneca redmanii , with mitochondrial 16S rRNA sequencing revealing 98.73% similarity among isolates (PQ580903-PQ580904). Water quality analysis of aquaculture ponds showed suboptimal conditions compared to the source irrigation canal, including elevated unionized ammonia (0.024–0.042 mg/L vs. 0.012 mg/L) and reduced dissolved oxygen (4.8–5.2 mg/L vs. 6.8 mg/L). Heavy metal accumulation followed consistent tissue-specific patterns (liver > gills > muscle) across five metals (Pb, Fe, Cu, Cd, Mn), with M. cephalus demonstrating the highest bioaccumulation potential. In M. cephalus liver tissue, transfer factors for Cu (175) and Fe (15.45) indicated significant metal retention. Correlation analysis in M. cephalus tissues revealed strong positive relationships between Cu-Fe ( r = 0.88) and Fe–Mn ( r = 0.78). The human health risk assessment indicated that muscle tissue consumption across all species was within safe limits (THQ ≤ 1.0). This integrated analysis provides insights into species-specific management strategies in Mediterranean aquaculture.

Sustainable and eco-friendly packaging films based on poly vinyl alcohol incorporated with Chrysanthemum frutescens extract - Mona M. AbdelMohsen; Hebat-Allah S. Tohamy; Sally A. Abdel-Halim; Hassan M. Awad; Mohamed El-Sakhawy (Natural Product Research, 2025)

Botulinum toxin type A: Efficacy in the management of lower limb spasticity in children with genetic disorders - Mohamed Ashraf; Dina Amin Saleh; Salma M Bakr; Mohamed Ali; George Halim; Marwa A Nassef; Nermine Farouk; Tamer M Sabry; Ahmed Abdellatif Awad; Mostafa G Mahran; Walid Abdel Ghany (Next Research, 2025)

Hydrogeophysical investigation for delineating groundwater aquifers in the Nabaa Al Hammara area, Wadi El Natrun, Egypt - SultanA.S. Araffa; Hassan H. El-Kadi; Abbas M. Abbas; Ahmed M. Al Dabour; Mahmoud S. Awad; Mahmoud Zayed (Journal of African Earth Sciences, 2025)

Melatonin and Strigolactone Combined Application Mitigate Salinity Stress Through Modulation of Antioxidants Defense Mechanism, Osmotic Adjustment and Ions Homeostasis in Maize Seedlings - Salman Aloufi; Basmah M. Alharbi; Abdul Sattar; Zahid Khorshid Abbas; Fahad Mohammed Alzuaibr; Nadi Awad Al-Harbi; Mohammed Alqurashi; Doaa Bahaa Eldin Darwish (Journal of Soil Science and Plant Nutrition, 2025)

Depositional and diagenetic drivers of heterogeneous reservoir quality in the Neogene strata of the Red Sea (Egypt) - Ahmed Ali; Ahmed Awad Abdelhady; Ramadan S. A. Mohamed; Douaa Fathy; Mohamed Hashem; Mohamed S. Ahmed; Sherif M. Aboueldahab; Mahmoud M. Khalil; Mohamed H. Farag (Carbonates and Evaporites, 2025)

Electrolyzed water as a microbial control measure for white soft cheese - Salwa M. Awad; Eman F. Abdel-latif; Khalid Sh Tolba; Huda Elsayed; Zeinab I. Ali; Adel M. Saudi (International Dairy Journal, 2025)

Protective role of curcumin and selenium nanoparticles against aluminium chloride-induced hepatorenal toxicity in rats - Safaa M. Awad; Yasser A. Attia; Akaber T. Keshta; Shimaa H. Watad; Eman Rashad; Hassan Elsayed; Shams H. Abdel-Hafez; Aziza T. Fathy (Journal of Molecular Histology, 2025)

Brine-saturated kaolinite mudrocks preserve capillary sealing to CO2 at high pressure and temperature - Mohamed M. Awad; D. Nicolas Espinoza (Marine and Petroleum Geology, 2025)

The Role of MicroRNAs in Neurodegeneration: Insights from Huntington’s Disease - Reda M. Mansour; Abanoub A. S. Shaker; Ahmed I. Abulsoud; Sherif S. Abdel Mageed; Alaa Ashraf; Elsayed G. E. Elsakka; Mohammed. I. Dahab; Mohamed M. Sadek; Farah A. Awad; Radwa H. Lutfy; Hanan Elimam; Ahmed H. I. Faraag; et al. (Molecular Neurobiology, 2025)

Projecting rice water footprint for different shared socioeconomic pathways under arid climate conditions - Elsayed Ahmed Elsadek; Diaa Eldin M. Elshikha; Ahmed Awad; Yousef Alhaj Hamoud; Ahmed Mohamed Elsheikha; Clinton Williams; Ethan Orr; Hiba Shaghaleh; Amar Ali Adam Hamad; Kelly R. Thorp; Ahmed Elbeltagi (Irrigation Science, 2025)

Torsional irregularity of NSC and HSC asymmetric multistory 3-D buildings - Ahmed M. Yousef; Ahmed A. Ghaleb; Doaa M. Awad; Mohamed Ghannam (Innovative Infrastructure Solutions, 2025)
The reliability of the criteria adopted by the seismic codes in the United States (ASCE/SEI-7-16), in Europe (EC-8) and Egypt (ECP201-2012), that are used in distinguish torsionally irregular from torsionally regular Normal-Strength Concrete (NSC) and High-Strength Concrete (HSC) multistory 3-D buildings have been studied. The Static Equivalent Lateral Force (SELF) methods used by these codes for predicting the torsional moments have been examined when applied to NSCand HSCtorsionally asymmetric multistory buildings. Finite element model has been used to solve the nonlinear equations of motions for two multistory buildings examples with different eccentricity (e equal to 0.10L i , 0.15L i and 0.20L i ) and constructed from NSC ( $$f_{c}^{′ }$$ f c ′ = 25 N/mm 2 ), HSC( $$f_{c}^{′ }$$ f c ′ up to 75 N/mm 2 ) and VHSC ( $$f_{c}^{′ }$$ f c ′ up to 100 N/mm 2 ). Many different earthquake records have been used in the seismic analysis. The results showed that the criteria adopted by ASCE/SEI-7-16 so as to distinguish torsionally regular from torsionally irregular NSC, HSC and VHSC multistory buildings are the most reliable and more simple and accurate when compared with the methods adopted by EC-8 and ECP201-2012. The provisions of ECP201-2012 for determination of the torsional irregularity of a building depending on the calculated structural eccentricity (between C. M. and C. R.) may lead to unsafe results. Using the SELF methods of the studied seismic codes in predicting the torsional moments of some torsionally symmetrical and torsionally asymmetrical multistory buildings constructed from NSCand HSCmay lead to unsafe and unconservative predictions. The value of the accidental eccentricity adopted by the studied seismic codes underestimated the torsional moments predicted using SELF methods of the studied codes in some torsionally symmetrical and torsionally asymmetrical multistory buildings.

Lysozyme Peptides as a Novel Nutra-Preservative to Control Some Food Poisoning and Food Spoilage Microorganisms - Adham M. Abdou; Dina A. B. Awad (Probiotics and Antimicrobial Proteins, 2025)
Foodborne illnesses and microbial food contamination are crucial concerns and still issues of great worldwide concern. Additionally, the serious health hazards associated with the use of chemical preservatives in food technology. Lysozyme (Lz) is an active protein against Gram-positive bacterial cell wall through its muramidase lytic activity; however, several authors could identify some antimicrobial peptides derived from Lz that have an exaggerated and broad-spectrum antibacterial activity. Therefore, a lysozyme peptides preparation (LzP) is developed to broaden the Lz spectrum. In this work, we investigated the potential efficacy of LzP as a novel Nutra-preservative (food origin) agent against some pathogenic and spoilage bacteria. Our results showed that LzP demonstrated only 11% of the lysozyme lytic activity. However, LzP exhibited strong antibacterial activity against Escherichia coli , Salmonella enteritidis , and Pseudomonas species, while Salmonella typhi and Aeromonas hydrophila exhibited slight resistance. Despite the lowest LzP concentration (0.1%) employed, it performs stronger antibacterial activity than weak organic acids (0.3%). Interestingly, the synergistic multi-component formulation (LzP, glycine, and citric acid) could inhibit 6 log 10 cfu/ml of E. coli survival growth. The effect of heat treatment on LzP showed a decrease in its antibacterial activity at 5 and 67% by boiling at 100 °C/30 min, and autoclaving at 121 °C/15 min; respectively. On the other hand, LzP acquired stable antibacterial activity at different pH values (4–7). In conclusion, LzP would be an innovative, natural, and food origin preservative to control the growth of food poisoning and spoilage bacteria in food instead chemical one.

Towards sustainability and circular economy: conceptual design model for the water-energy-food nexus in Ferdaws Village, Western Desert, Egypt - Noha M. Mashaal; Mohamed A. Abdelzaher; Mohamed M. Awad; Khalid Z. Elwakeel; Ahmed A. Hassan (Innovative Infrastructure Solutions, 2025)
Sustainable management of natural resources is a pressing global challenge that requires the prevention of loss and waste. Egypt is facing an acute water crisis due to insufficient water supplies throughout the country. To address this issue, it is essential to implement a range of solutions to improve the situation. This study aims to alleviate the stress on multiple resources and environmental impacts in one of Egypt's earliest reclaimed areas (Wadi El-Natrun, Western Desert), by applying systematic modeling to achieve sustainable development objectives and mitigate resource stress. To promote a more sustainable and resilient future, a pilot model ecovillage has been designed for a community of three thousand inhabitants, promoting integrated resource management and considering the Water-Energy-Food (WEF) nexus concept. The ecovillage design incorporates collaborative engagement of groundwater reservoirs for water supply, agricultural production for food demands, power generation, and community sensitivity. Evaluating key aspects related to water supply, power generation, agricultural production, and environmental impact within the proposed pilot design aims to provide insights into the complex interactions among these systems. A four-step methodology for evaluating and implementing the nexus at a local level, which includes identifying linkages, mapping interconnections, focusing on core foundations, and applying the findings to improve project execution was investigated. An understanding of the WEF nexus, demonstrating how such frameworks can enhance the management of scarce resources was provided. The “TORAY DS2” design is employed to analyze model parameters and quantify their values. The study’s findings aim to support decision-makers and stakeholders in developing effective strategies to navigate the complexities of the WEF Nexus, promoting optimal resource management. These findings are promising, indicating a low environmental risk while aligning with both the WEF Nexus and the Sustainable Development Goals.

A deep deterministic policy gradient approach for optimizing feeding rates and water quality management in recirculating aquaculture systems - Wael M. Elmessery; Said Elshahat Abdallah; Awad Ali Tayoush Oraiath; Víctor Espinosa; Mohamed Fawzi Abdalshefie Abuhussein; Péter Szűcs; Mohamed Hamdy Eid; Doaa M. El-Shinawy; Huda Aljumayi; Samy F. Mahmoud; Abdallah Elshawadfy Elwakeel (Aquaculture International, 2025)
Optimizing feeding rates in recirculating aquaculture systems (RAS) is crucial for ensuring fish growth, health, and system efficiency. This research introduces a novel approach to RAS feeding control using a Deep Deterministic Policy Gradient (DDPG) reinforcement learning algorithm. The developed system integrates feeding rate optimization with comprehensive water quality management to improve overall performance and stability. The DDPG controller demonstrated superior tracking accuracy, reduced feed consumption, and improved operational stability compared to traditional control methods such as Model Predictive Control (MPC), PID, and Bang-Bang control. The learned policy-maintained feeding rates within optimal ranges while adapting to dynamic system requirements and environmental conditions. The integration of water quality monitoring and control further enhanced system stability, ensuring critical parameters remained within target ranges. Comparative analysis revealed the DDPG controller’s advantages in terms of faster recovery times after environmental perturbations, improved long-term stability, and significant economic benefits through reduced operational costs and increased efficiency. The robustness and adaptability of the system were validated through comprehensive testing under various fault conditions, growth phases, and system scales. The successful development and evaluation of the DDPG-based RAS feeding control system represents a significant advancement in aquaculture management. The demonstrated improvements in efficiency, stability, and economic performance establish the potential for this approach to revolutionize feeding practices in commercial RAS operations. Further research and development efforts can build upon these findings to advance the state-of-the-art in intelligent aquaculture management systems and promote the sustainability and profitability of the industry.

In Vitro and In Vivo Appraisal of Glycerylmonostearate/chitosan Hybrid Nanocapsules As Peroral Delivery System of Simvastatin - Mohammed Elmowafy; Khaled Shalaby; Nabil K. Alruwaili; Omar Awad Alsaidan; Mohammed H. Elkomy; Mohamed A. Abdelgawad; Ehab M. Mostafa; Ayman Salama; Abdulsalam M. Kassem; Mohamed F. Ibrahim; Mahran Mohamed Abd El-Emam (AAPS PharmSciTech, 2025)

Ostracod and foraminiferal assemblages in Tébessa (Northeast Algeria): Insights into Santonian cooling effects - Sakina Nemouchi; Sihem Salmi-Laouar; Ahmed Awad Abdelhady; Amor Deghaichia; Mostafa M. Sayed; Youssef Bazeen; Michael Hesemann; Mohamed Ahmed; Mabrouk Boughdiri (Marine Micropaleontology, 2025)

Insecticidal activity and systematic insights of carvacrol against Tribolium castaneum: Acetylcholinesterase inhibition, oxidative stress, and molecular docking" - Hassan M. Eltalawy; Huda El-Fayoumi; Shawky M. Aboelhadid; Saleh Al-Quraishy; Almahy M. El-Mallah; Fatma I. Abo El-Ela; Ezzat M. Awad; Abdel-Azeem S. Abdel-Baki (Journal of Stored Products Research, 2025)

Distribution of recent ostracods and benthic foraminifera from Farwa Lagoon (NW Libya) - Sherif M. El Baz; Abdalla Shahin; Ahmed Al Furjany; Hatem Aboelkhair; Asmaa Awad (Journal of African Earth Sciences, 2025)

Long-term performance of polyethylene geomembranes to contain brine - M. Zafari; R. Kerry Rowe; R. Awad (Geotextiles and Geomembranes, 2025)

Variability in Saharan cyclone tracks, I: climatology study - Abdulhaleem H. Labban; Adel M. Awad (Meteorology and Atmospheric Physics, 2025)

Efficacy of curcumin-selenium nanoemulsion in alleviating oxidative damage induced by aluminum chloride in a rat model of Alzheimer’s disease - Safaa M. Awad; Yasser A. Attia; Hassan ElSayed; Shams H. Abdelhafez; Akaber T. Keshta; Eman Rashad; Heba M. A. Khalil; Aziza T. Fathy (Journal of Molecular Histology, 2025)

Phytochemicals in pomegranate peel extract attenuate oxidative damage in rats exposed to fipronil - Awad R. Abd Elfatah; Marwa E. Hassan; Yasmin E. Abdel-Mobdy; Osama M. Abd El fatah; Emam A. Abdelrahim; Mosaad A. Abdel-Wahhab (Pesticide Biochemistry and Physiology, 2025)

The Gastroprotective Effects of Salvia indica L. and Selenium In Vivo Study - Talal Salem Al-Qaisi; Ahmed A. J. Jabbar; Mohammed M. Hussein M. Raouf; Parween Abdul-Samad Ismail; Ramzi A. Mothana; Hanan M. Al-Yousef; Rawaz Rizgar Hassan; Mahmood Ameen Abdulla; Musher Ismael Saleh; Mohammed Awad; Mohamad Fawzi Mahomoodally (Biological Trace Element Research, 2025)

Investigating the role of ENSO in groundwater temporal variability across Abu Dhabi Emirate, United Arab Emirates using machine learning algorithms - Khaled Alghafli; Xiaogang Shi; William Sloan; Awad M. Ali (Groundwater for Sustainable Development, 2025)

Antibacterial and cytotoxic activities of a newly green synthesized ZnO/Se nanocomposite combined with Washingtonia robusta H. Wendl fruit extract - Rolla M. Fayed; Zakaria Awad Mohamed Baka; Basma Hamdy Farouk; Mohamed Marzouk El-Zahed (Biocatalysis and Agricultural Biotechnology, 2025)

Persimmon (Diospyros kaki L.) leaves accelerates skin tissue regeneration in excisional wound model: possible molecular mechanisms - Talal Salem H. Al-Qaisi; Ahmed A. j. Jabbar; Mohammed M. Hussein M. Raouf; Parween AbdulSamad Ismail; Ramzi A. Mothana; Mohammed F. Hawwal; Rawaz Rizgar Hassan; Mahmood Ameen Abdulla; Musher Ismael Saleh; Mohammed Awad (Journal of Molecular Histology, 2025)

Performance of a recirculating aquaponic system in vegetable production using river fish (Nile tilapia) - Mohamed I. Saber; Noha A. Mahgoub; Yasser M. Awad; Samira R. Mansour (Euro-Mediterranean Journal for Environmental Integration, 2025)

Safety and efficacy of dasotraline for patients with attention deficit/hyperactivity disorder: a systematic review and meta-analysis of 1594 patients including GRADE qualifications - Mohamed Ezzat M. Mansour; Khalid Radwan Alsaadany; Mohamed Awad E. Ahmed; Ahmed Ezzat Elmetwalli (Psychopharmacology, 2025)

Detection and molecular insights into the azurin gene expression post– gamma irradiation in P. aeruginosa - Ebthag M. Awad; Nagwa A. Abdallah; Mona M. K. Shehata; Hala A. Farrag (Archives of Microbiology, 2025)

Correction to: The effects of nano‑selenium and/or vitamin C on the growth performance, blood health, organ histology, molecular alterations, and disease resistance of Nile tilapia (Oreochromis niloticus) against Saprolegnia ferax - Hayat Ali Alafari; Najah M. Albaqami; Yasmin M. Abd El‑Aziz; Yasmin A. Reyad; El‑Sayed Hemdan Eissa; Zulhisyam Abdul Kari; Moaheda E. H. Eissa; Saadiah Ibrahim; Saleha Khan; Mohammad Bodrul Munir; Abdelazeem M. Algammal; Ismail Youssef; et al. (Aquaculture International, 2025)

The effects of nano-selenium and/or vitamin C on the growth performance, blood health, organ histology, molecular alterations, and disease resistance of Nile tilapia (Oreochromis niloticus) against Saprolegnia ferax - Hayat Ali Alafari; Najah M. Albaqami; Yasmin M. Abd El-Aziz; Yasmin A. Reyad; El-Sayed Hemdan Eissa; Zulhisyam Abdul Kari; Moaheda E. H. Eissa; Saadiah Ibrahim; Saleha Khan; Mohammad Bodrul Munir; Abdelazeem M. Algammal; Ismail Youssef; et al. (Aquaculture International, 2025)

First Record of Five Species of Sea Urchins (Class Echinoidea, Five Orders) From the Gulf of Aden - Mohammed A. Algurabi; Alawi H. MсNoon; Rashidi M. R. Awad; Shima Bakhshalizadeh; Botagoz M. Nasibulina; Tatyana F. Kurochkina; Attaala M. Ali; Syed Sikandar Habib; Francesco Fazio (Marine Ecology, 2025)
The Gulf of Aden (GA) experiences seasonal upwelling phenomena, fostering favorable conditions for diverse marine life. Despite this richness, the known sea urchin species in the Gulf of Aden has been limited to the common long‐spined ( Diadema paucispinum ). Our study aimed to explore and document sea urchin diversity in this region. Through scuba diving and low tide collections from coral reefs and sandbanks, we obtained samples along the Hadhramout coast, spanning from the Qusayr area to the Aden Province coast, including Azizi Island opposite Ras Imran and the sub‐district of the city of Aden. This survey revealed five sea urchin species, expanding the known taxa. For the first time in the Gulf of Aden, we qualitatively registered two regular and three irregular sea urchin species: Heterocentrotus mammillatus (Linnaeus, 1758), Stomopneustes variolaris (Lamarck, 1816), Echinodiscus bisperforatus (Leske, 1778), Clypeaster humilis (Leask, 1778), and Lovenia elongata (Gray, 1845). These findings contribute to our understanding of the Gulf biodiversity and emphasize the need for continued exploration in this region.

Quality maintenance of Washington navel oranges and control of fungal decay using CaCl₂, chitosan, and Rhodotorula mucilaginosa treatments - Mohamed I. Elsayed; Najeeb M. Almasoudi; Mohamed A. Awad; Adel D. Al-Qurashi; Kamal A. M. Abo-Elyousr (Journal of Plant Pathology, 2024)

Adsorptive performance of bismuth-doped Ni-Zn-Co ferrite nanoparticles for the removal of methylene blue dye - Dema Dasuki; Amani Aridi; Marwa Elkady; Khulud Habanjar; Gehan M. El-Subruiti; Ramadan Awad (Environmental Science and Pollution Research, 2024)

The Preventive Effect of Zinc Sulfate against Olanzapine-Induced Testicular Toxicity in Male Rats - Hossam Ebaid; Samir A. E. Bashandy; Iftekhar Hassan; Jameel Al-Tamimi; Shimaa Abdallah Haredy; Tharwat Imbabi; Enayat A. Omara; Yousef S. Bashandy; Ezzat M. Awad (Biological Trace Element Research, 2024)
Male infertility is a complex and multifactorial clinical condition affecting a large population attributed to several factors, including perturbation in oxidative stress and the level of essential trace elements. Oxidative stress exerts multiple issues related to reproductive health, including male infertility, decreased sperm motility, sperm DNA damage, and an increased susceptibility to genetic disorders. Besides chemical toxins and food allergens in junk food items, many drugs can also lead to male infertility. Olanzapine (OLZ), a general antipsychotic drug, has also been reported to induce male fertility. A great deal of literature entails that supplementation of zinc can alleviate oxidative stress–related clinical complications, including male infertility. This study investigates the potential protective effects of zinc sulfate (ZnSO4) on OLZ-induced male infertility. In the present study, there were four treatment groups ( n = 6): group 1 as control (without any treatment); group 2 treated with OLZ (10 mg/kg) orally daily for 6 weeks; groups 3 and 4 treated with 50 mg/kg and 100 mg/kg of ZnSO4 respectively in pre-exposed OLZ (10 mg/kg) orally daily for 6 weeks. After completion of the treatment, the biochemical analysis of serum and tissue samples demonstrated that group 2 had compromised levels of antioxidant parameters (superoxide dismutase (SOD), catalase (CAT), and reduced glutathione (GSH)) as well as elevated levels of stress parameters (oxidized glutathione (GSSG), malondialdehyde (MDA), and nitric oxide (NO)) as compared to the control by a significant extent ( p ≤ 0.05). However, supplementation of ZnSO4 significantly corrected all these parameters in a dose-dependent way in groups 3 and 4 ( p ≤ 0.05). Other health indicators, like taurine, enzyme Q10, phosphatidylcholine, ascorbic acid, and vitamin E, were also observed to improve prominently with the supplementation of ZnSO4. Intriguingly, all the fertility parameters (sperm motility, count and level of testosterone) were also found to be significantly enhanced with decreased sperm abnormalities in both the combination groups. The histological evaluation of the testis section also agreed with the biochemical analysis in this investigation. Therefore, the study strongly advocates that supplementation of Zn can ameliorate OLZ-induced male infertility to a significant extent. Graphical Abstract Putative mechanism was involved in a preventive effect of ZnSO4 against OLZ-induced biochemical and histological perturbation in vivo. OLZ generates free radicals to induce oxidative stress-mediated toxicity in all target organs including testes evidenced by alteration in biochemical markers and histology. Zn ions from ZnSO4 act as an antioxidant agent blunting most of the OLZ-perturbed redox markers and histology consequently improving fertility parameters.

Recent advances and future prospects of MXene-based photocatalysts in environmental remediations - Basiru O. Yusuf; Mustapha Umar; Mansur Aliyu; Aliyu M. Alhassan; Mohammed Mosaad Awad; Omer A. Taialla; AbdulHakam Shafiu Abdullahi; Jamilu Nura Musa; Khalid R. Alhooshani; Saheed A. Ganiyu (Journal of Environmental Chemical Engineering, 2024)

Assessment of Ocean Acidification Impact on Gastropod Shells Using Geometric Morphometrics - Ahmed Awad Abdelhady; Mohamed S. Ahmed; Mohamed Samy-Kamal; Ali. M. Hussain (Water, Air, & Soil Pollution, 2024)

Association between the variations in metabolic pathways and oral cancer risk: results from a Pakistani case-control study - Arifa Shabbir; Muhammad Usman Rashid; Ezzat M. Awad; Humaira Naeemi; Talin Barisani-Asenbauer; Naila Malkani (Molecular Biology Reports, 2024)

Foliar Nourishment with Different Potassium Sources to Maximize Yield Through Improving Nutrient Uptake in Citrus Aurantifolia Trees Grown in Potassium-Deficient Soil - Ahmed A. M. Awad; Hamdy A. Z. Hussein; Asmaa G. A. Abd El Samad; Hussein E. E. Belal; Hamada R. Beheiry (Journal of Soil Science and Plant Nutrition, 2024)
Purpose: Based on its crucial regulatory role in several biochemical processes, potassium (K) is considered to greatly influence fruit yield and quality. Methods: Two field experiments were carried out in two seasons (2021 and 2022) to explore the response of lemon (Baladi cv.) trees grown in K-deficient soil to four different K fertilizer sources applied individually as a foliar spray. K citrate (KC 1 = 1.3 vs. KC 2 = 2.6 g L − 1 ), K nitrate (KN 1 = 1.5 vs. KN 2 = 3.0 g L − 1 ), K tartrate (KT 1 = 1.5 vs. KT 2 = 3.0 g L − 1 ), and K thiosulfate (KS 1 = 1.25 vs. KS 2 = 2.5 g L − 1 ) were applied three times, and the treated trees were compared with untreated trees. This study was established with a randomized complete block design (RCBD) using four replicates. Results: The findings revealed that the KC treatment, regardless of dosage, showed clear superiority in terms of the values for the leaf phosphorus (%), manganese, and zinc contents (mg kg − 1 ), as well as fruit firmness, fruit dry matter, and total soluble solids in both seasons. In second place was the KT treatment, which yielded the best values for fruit length and width in 2021, the best values for leaf nitrogen and iron contents and fruit weight and volume in 2022, and the best values regarding variable fluorescence by maximum fluorescence, relative chlorophyll content (SPAD readings), the photosynthetic performance index, total acidity, and vitamin C in both seasons. Furthermore, the highest total lemon yield and leaf potassium contents were achieved with the KN treatment in both seasons. The heat map illustrating that most of the studied characteristics were positively and significantly correlated with total lemon yield (TLY). Conclusions: The KN treatment, closely followed by the KC treatment, is regarded to be the best treatment for most of the studied trails.

Application of Biostimulants Alleviated Drought Stress in Sugar Beet (Beta vulgaris L.) by Improving Oxidative Defense System, Osmolytes Accumulation and Root Yield - Abdul Sattar; Ahmed Abou El-Yazied; Basmah M. Alharbi; Hany G. Abd El-Gawad; Zahid Khorshid Abbas; Karima Mohamed El-Absy; Samy F. Mahmoud; Mohammed M. Althaqafi; Doaa Bahaa Eldin Darwish; Nadi Awad Al-Harbi; Qasim Ali; Mohamed F. M. Ibrahim (Journal of Soil Science and Plant Nutrition, 2024)

Fog collection rate investigation for a hydrophobic surface and different inclinations of rectangular meshes - Abdullah A. Elshennawy; Magdy Y. Abdelaal; Ahmed M. Hamed; Mohamed M. Awad (Euro-Mediterranean Journal for Environmental Integration, 2024)

Influence of Mg-doped Ni0.33Zn0.33Co0.33Fe2O4 Nanoparticles on the Methylene Blue Adsorption Efficiency Under Various Operational Parameters - Dema Dasuki; Amani Aridi; Marwa Elkady; Khulud Habanjar; Gehan M. El-Subruiti; Ramadan Awad (Water, Air, & Soil Pollution, 2024)

Neurotoxicity, Cytotoxicity, and Genotoxicity of Phyto-radio Synthesized Selenium Nanoparticles in Culex pipiens Complex - H. H. Awad; I. Abulyazid; E. M. S. El-Kholy; H. S. Mohammed; H. K. Abdelhakim; A. M. Fadl (Biological Trace Element Research, 2024)
Effective mosquito management strategies are crucial to minimize the number of mosquito-borne diseases. Selenium nanoparticles (SeNPs) are promising in mosquito control because they are effective and eco-friendly rather than synthetic insecticides. The current study was conducted to evaluate the impact of SeNPs on the detoxification enzymes, acetylcholine esterase (AChE), glutathione S-transferase (GST), and α-carboxyl esterase (α-CarE), in larval instars of Culex pipiens complex at the LC 50 concentration. In 3rd instar larvae treated with microwave-assisted selenium nanoparticles (SeNPs-MW) and gamma-assisted selenium nanoparticles (SeNPs-G), it was found that AChE activity was significantly inhibited. On the other hand, significant increases in GST and α-CarE activities were observed. Additionally, genotoxic and ultrastructure studies of midgut epithelial cells in 3rd instar larvae revealed DNA damage and cell lysis, including destruction of the cell membrane, microvilli, and nuclei. These findings suggest that SeNPs have an adverse effect on AChE gene expression, resulting in its downregulation. This downregulation can be attributed to the formation of reactive oxygen species induced by SeNPs that can modulate the host defense mechanism leading to apoptosis and subsequent larval mortality. The present study was the first to use phyto-microwave-assisted and gamma-assisted synthesis of SeNPs which provides an eco-friendly and cost-effective solution to reduce the risk of chemical insecticides. Furthermore, an integrated pest management program (IPM) using nanocides can be successfully developed for mosquito control.

Navigating the impact of remittances on environmental quality in Africa: The crucial role of institutional quality - Atif Awad; Ebaidalla M. Ebaidalla; Sara Yasin; Ilhan Ozturk (Journal of Environmental Management, 2024)

Correction: Comprehensive approach integrating water quality index and toxic element analysis for environmental and health risk assessment enhanced by simulation techniques - Mohamed Hamdy Eid; Mahmoud Awad; Essam A. Mohamed; Tamer Nassar; Mostafa R. Abukhadra; Ahmed M. El-Sherbeeny; Attila Kovács; Péter Szűcs (Environmental Geochemistry and Health, 2024)

Comprehensive approach integrating water quality index and toxic element analysis for environmental and health risk assessment enhanced by simulation techniques - Mohamed Hamdy Eid; Mahmoud Awad; Essam A. Mohamed; Tamer Nassar; Mostafa R. Abukhadra; Ahmed M. El-Sherbeeny; Attila Kovács; Péter Szűcs (Environmental Geochemistry and Health, 2024)
Due to water shortages and the potential impact of Ethiopia’s new dam on the Nile River, Egypt is seeking new water resources. This study assesses the drinking water quality and associated risks from potentially toxic elements (PTEs) in the Quaternary aquifer (QA) in Beni-Suef, Egypt. Using a comprehensive approach, including PHREEQC geochemical modeling, ionic ratios, multivariate statistical analyses, and the integrated weight water quality index (WQI), the study evaluated the sources of ion contamination and the mixing of Nile water with QA. Various indices, such as the Heavy Metal Pollution Index (HPI), ecological Risk Index (RI), Hazard Quotient (HQ), and Hazard Index (HI), were used to assess ecological and health risks. Monte Carlo simulations provided probabilistic assessments of non-carcinogenic risks for adults and children. GIS tools were used to map risk indices, identifying the most deteriorated locations for sustainable management. The hydrochemical analysis revealed water facies including Na–Cl, Ca–Mg–HCO 3 , and mixed types, influenced by carbonate dissolution, ion exchange, and silicate weathering. Contamination sources, particularly in the north and south, were linked to agricultural activities, irrigation return flow, municipal waste, and evaporation. The WQI indicated that 10.14% of samples were extremely poor, 21.7% were poor, 26% were medium, and 42% were good to excellent. PTE contamination varied, with HPI values indicating good water quality in the central area in 53.6% of the collected samples (HPI < 30), but contamination in the north and south is high (HPI > 51). Ecological Risk Index values were below the threshold in 100% of samples (RI < 30), confirming water safety regarding PTEs. In comparison, for hazard index (HI) through oral/ingestion, adults exhibited HI values ranging from 0.012 to 2.16, while children showed higher values, ranging from 0.045 to 8.25. However, the hazard index for oral/ingestion exceeded safe limits in the north and south (HI oral > 1), posing non-carcinogenic risks. Monte Carlo simulations revealed significant risks from oral exposure to manganese (HQ oral > 1), particularly in El-Wasta and El-Fashn, necessitating further treatment and management.

Efficacy and Safety of Ontamalimab in Treating Inflammatory Bowel Disease: a Systematic Review and Meta-Analysis of Randomized Controlled Trials - Abdelaziz A. Awad; Menna M. Aboelkhier; Rashad G. Mohamed; Ahmed W. Abbas; Ahmed W. Hageen; Yousef R. Alnomani; Mohamed Abouzid (Current Pharmacology Reports, 2024)
Purpose of Review Ontamalimab is an anti-MAdCAM-1 monoclonal antibody. It directly restricts the binding of α4β7 + lymphocytes and does not affect the homing of lymphocytes in the central nervous system. Thus, it diminishes adverse effects while blocking their migration into the gut. Several clinical trials have validated the efficacy and safety of ontamalimab for Crohn's disease and ulcerative colitis. However, to date, there is no meta-analysis on the topic. Hence, we are conducting this meta-analysis. Using R version R.3.3, we reported outcomes as risk ratios (RRs) or mean difference (MD) and confidence intervals (CIs). A P -value ≤ 0.05 is considered as statistically significant. Recent Findings The meta-analysis included a total of three studies with 1384 patients. In patients with ulcerative colitis, compared to placebo, ontamalimab had significantly improved clinical remission (RR = 2.17, 95% CI [1.42 to 3.32], P < 0.01), clinical response (RR = 1.79, 95% CI [1.35 to 2.38], P < 0.01), endoscopic response (RR = 2.27, 95% CI [1.55 to 3.31], P < 0.01) and mucosal healing (RR = 2.39, 95% CI [1.63 to 3.50], P < 0.01). No significant differences favoring ontamalimab or the placebo were found regarding safety outcomes. In patients with Crohn's disease, ontamalimab showed superiority over placebo in endoscopic response (RR = 2.00, 95% CI [1.08 to 3.70], P = 0.03). However, ontamalimab was associated with a higher incidence of serious adverse events, and study discontinuations were due to adverse events. Summary Ontamalimab has shown promising results, particularly in patients with moderate to severe ulcerative colitis, as evidenced by better clinical response and remission. However, questions remain about its long-term effectiveness and safety; hence, extended follow-up and more extensive studies are necessary.

Molecular characterization of elite olive cultivars grown in the North region of Saudi Arabia using SCoT, ISSR, and SRAP techniques - Reem M. Alharbi; Nanis H. Gomah; Wafik S.M. Ragab; Nabil S. Awad; Mohamed A. Abdein (Biocatalysis and Agricultural Biotechnology, 2024)

Exogenous Application of Tyrosine Mitigated the Adversities of Drought Stress in Maize Seedlings through Modulation of Photosynthetic Performance and Antioxidants Defense Systems - Mohamed M. El-Mogy; Abdul Sattar; Qasim Ali; Basmah M. Alharbi; Zahid Khorshid Abbas; Siham M. AL-Balawi; Mohammed M Althaqafi; Nadi Awad Al-Harb; Salem Mesfir Al-Qahtani; Doaa Bahaa Eldin Darwish (Journal of Soil Science and Plant Nutrition, 2024)

Potentiality of Melatonin for Reinforcing Salinity Tolerance in Sorghum Seedlings via Boosting Photosynthetic Pigments, Ionic and Osmotic Homeostasis and Reducing the Carbonyl/Oxidative Stress Markers - Nesma M. Helal; Hani S. Saudy; Maha M. A. Hamada; Ahmed Abou El-Yazied; Hany G. Abd El-Gawad; Soumya Mukherjee; Salem Mesfir Al-Qahtani; Nadi Awad Al-Harbi; Salwa M. El-Sayed; Mohamed F. M. Ibrahim (Journal of Soil Science and Plant Nutrition, 2024)
Salinity stress has become a major threat to worldwide crop production. Exogenous melatonin (MT) has appeared as a promising treatment against salt stress in several plant species. However, MT effect on the tolerance of sorghum plants under different saline conditions (moderate and severe) remains ambiguous. This study was carried out to explore the impact of MT (0, 50, 100 and 200 µM) as a foliar application on sorghum seedlings grown under moderate and severe saline conditions using sodium chloride, NaCl (75 and 150 µM NaCl). Salinity treatments were applied as solution in sand medium in pots. The results demonstrated that rising salinity level negatively affected plant growth, photosynthetic pigments (chlorophylls and carotenoids), leaf water status and ionic homeostasis (sodium, potassium, and calcium ions). Applied-MT specifically at 100 or 200 µM enhanced the osmotic balance, cell membrane stabilizing and leaf relative water content. These effects were associated with an obvious restriction to the level of hydrogen peroxide, lipid peroxidation (malondialdehyde content) and methylglyoxal. Moreover, antioxidant activities of peroxidase, catalase, superoxide dismutase, and ascorbate peroxidase enzymes were modulated by MT treatments. Molecular docking modeling assessment illustrated top-ranked confirmations between MT and the target antioxidant enzymes. MT forms multiple hydrogen bonds with key amino acid residues for glycine (A: 162), tryptophan (A: 41), leucine (A: 165), tyrosine (A: 235) in the active site of ascorbate peroxidase. The alkyl interactions with leucine (A: 37), arginine (A: 38) and cysteine (A: 168) also contribute to its high affinity. Despite sorghum plant is commonly moderately tolerant to salinity stress, the results of this study confirmed its high sensitivity to a wide range of saline conditions at early growth stages. Melatonin spraying led to improvements in various morphological, physiological and biochemical mechanisms that harmonized together to confer stress resistance to salt-stressed sorghum seedlings.

Pathway to environmental sustainability: Assessing the role of productive capacity, remittances, and uncertainty in sub-Saharan Africa - Atif Awad; Mohamed AL Baity; Ilhan Ozturk; M. Azhar Hussain; Abdel Rahman Ahmed Abdel Rahman (Journal of Environmental Management, 2024)

Genome-wide identification and characterization of the dof gene family in mango (Mangifera indica L.) - Suliman M. S. Alghanem; Ghalia S. H. Alnusairi; Mariam Abdulaziz Alkhateeb; Khairiah Mubarak Alwutayd; Abdullah Alaklabi; Basmah M. Alharbi; Doha Abdullah Albalawi; Dikhnah Alshehri; Nadi Awad Al-Harbi; Salem Mesfir Al-Qahtani; Mona H. Soliman (Genetic Resources and Crop Evolution, 2024)

Atorvastatin loaded lecithin-coated zein nanoparticles based thermogel for the intra-articular management of osteoarthritis: in-silico, in-vitro, and in-vivo studies - Heba Amin Elgendy; Amna M. A. Makky; Yara E. Elakkad; Heba H. Awad; Mahmoud A. El Hassab; Nihal Farid Younes (Journal of Pharmaceutical Investigation, 2024)
Purpose Up-to-date literature offers limited data about utilizing atorvastatin calcium (ATV) as a promising chondroprotective agent in osteoarthritis (OA). So, this study aims to develop a depot intra-articular (IA) delivery system for ATV to enhance its deposition in the articular joint. Methods A 3 3 D-optimal design was implemented to prepare ATV-loaded lecithin-coated zein nanoparticles. The optimized formulation (Opt-LCZN) was selected and imaged using a transmission electron microscope according to the desirability value. Various in-vitro and in-silico studies were conducted to evaluate the features of Opt-LCZN. Additionally, it was loaded into an injectable thermogel (Opt-LCZN-thermogel) and evaluated in-vivo in OA-induced Sprague Dawley rats. Results The Opt-LCZN showed entrapment efficiency of 70.00 ± 2.96%, particle size of 191.95 ± 17.42 nm, zeta potential of − 20.12 ± 0.79 mV, and polydispersity index of 0.25 ± 0.01. The docking studies revealed favorable binding of zein and ATV, confirmed by molecular dynamics simulation. The morphological examination displayed a bilayer spherical structure formed of a zein core enclosed by a lecithin coat. Furthermore, the formulated Opt-LCZN-thermogel achieved a remarkable sustained release profile, with nearly 50% of the drug being released over 144 h. Opt-LCZN-thermogel showed a significant reduction in inflammation in OA-induced rats, confirmed by knee joint swelling and knee bend test results, in addition to the pro-inflammatory and anti-inflammatory mediators’ levels. The protective effect of ATV can be markedly observed through histopathological examination. Conclusion Based on these outcomes, the formulated IA delivery system of ATV can be presented as an excellent candidate for ameliorating OA. Graphical abstract

Mudrock wettability at pressure and temperature conditions for CO2 geological storage - Mohamed M. Awad; D. Nicolas Espinoza (International Journal of Greenhouse Gas Control, 2024)

Sensing the invisible: Ultrasensitive and selective colorimetric detection of E. coli O157:H7 based on masking the peroxidase-mimetic activity of aptamer-modified Au/Fe3O4 - Ramadan Ali; Abdullah Alattar; Reem Alshaman; Abduallh Ghabban; Sultan Alanazi; Hazem Al-Brahimi; Mohammed Alatwi; Abdullah Jlawi; Abdulmohsen Albalawi; Ahmed Moutair Awad Alatawi; Budor Al balawi; Afnan Al-Marwani; et al. (Food Chemistry, 2024)

New uricase producing Stenotrophomonas isolate recovered from a hot well in western south Egypt: Strain identification, Statistical optimization of enzyme production and In vitro application in gout treatment - Asmaa I. El-Shazly; Hassan M. Awad; Amira A. Gamal; Douaa H. Abdel-Aziz; Azza M. Noor El-Deen (Biocatalysis and Agricultural Biotechnology, 2024)

The vegetation around the foothills of the Hijaz Mountains, Saudi Arabia - Nick Hofland; Mohamed Z. Hatim; Jacob Thomas; John A. M. Janssen; Awad S. Alharti; Ahmed H. Alfarhan; Abdulrahman A. Alatar; Joop H. J. Schaminée; Mohamed A. El-Sheikh (Rendiconti Lincei. Scienze Fisiche e Naturali, 2024)
Despite Saudi Arabia being an interesting area from a floristic perspective, its vegetation is still relatively poorly studied. This certainly applies to the Hijaz Mountains and adjacent coastal zones. We aim to describe the flora and vegetation of the foothills of the Hijaz Mountains regarding the environmental conditions. Hijaz Mountains and adjacent coastal zones, Saudi Arabia. We studied the vegetation at the Hijaz Mountains’ foothills along two transects of vegetation surveys, one along the coast and one more inland. In addition, soil samples were taken and analyzed for soil texture, pH, electrical conductivity, organic matter, calcium carbonate and the concentration of the elements N, Na, K, Ca, Mg, Fe and Mn were determined. We calculated the data clustering tendency (Hopkins’ test analysis) and its optimal number of clusters (Elbow method). We used modified TWINSPAN to cluster the data and validated the resulting communities using the Silhouette algorithm. Seven plant communities resulted, each one dominated by a different plant species, namely: Haloxylon salicornicum , Lycium shawii , Senegalia hamulosa , Vachellia tortilis , Zygophyllum coccineum , Vachellia flava and Stipagrostis plumosa , and were described based on their floristic composition and could be further grouped into three vegetation clusters. The communities had varying ranges of occurrence in the study area, some dominating certain sections, with latitude and altitude being the biggest distinguishing environmental variables between the communities. We present a description of the vegetation of the Hijaz Mountains foothills. Our study is considered an important basis for decision-making of nature conservation and in-depth surveys of the area. Graphic abstract

Comparison of various hormone combinations and the potential of chitosan nanoparticles for growth stimulation in Astragalus spp. - Haifa A. S. Alhaithloul; Nabil S. Awad; Tahsin Shoala; Mesfer M. Alqahtani; Fahad Mohammed Alzuaibr; Abdulrahman Alasmari; Mohamed A. Abdein (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Integrating facies, mineralogy, and paleomagnetism to constrain the age and provenance of Paleozoic siliciclastic sedimentary rocks along the northern Gondwana margin: insights from the Araba and Naqus formations in western Gulf of Suez, Egypt - Ashraf M. Al-Nashar; Nabil A. Abdel Hafez; Mohamed W. Abd El-Moghny; Ahmed Awad; Sherif Farouk; Haitham M. Ayyad (International Journal of Earth Sciences, 2024)
The depositional ages and provenance of the Paleozoic Araba and Naqus Formations along the northern Gondwanan margin in Egypt have remained uncertain due to a lack of index fossils. Resolving this issue is crucial for understanding regional geology during deposition and subsequent tectonic development. We integrate detailed facies analysis, anisotropy of magnetic susceptibility (AMS), paleomagnetism, and mineralogical data to elucidate the genesis and depositional ages of the Araba and Naqus Formations. Petrographic analyses identified seven distinct facies types, providing insights into sedimentary textures, maturity, and sources, with contributions from igneous and metamorphic sources indicated by heavy minerals. X-ray diffraction (XRD) analysis identified accessory minerals such as quartz, goethite, kaolinite, hematite, and anatase. Paleomagnetism isolated two magnetic components ( C A and C N ) providing the first robust paleo pole positions at Lat. = 70.8° N, Long. = 308.2° E and Lat. = 37.8° N, Long. = 233.1° E, indicating Cambrian and Carboniferous ages for the Araba and Naqus formations, respectively. Thermal demagnetization constrained these dates using established polarity timescales. Mineralogical data indicated that the Araba Formation originated from an igneous source, while the Naqus Formation had a mixed metamorphic-igneous provenance. The integrated AMS and paleomagnetic data reveal evidence of post-depositional deformation. Specifically, the clustering of maximum AMS axes in the NW–SE direction for both formations, suggests the initial presence of a primary depositional fabric. However, prevalent tectonic activity during the Cenozoic appears to have overprinted and modified this fabric through deformation related to rifting of the Gulf of Suez region. Through this novel multi-proxy approach, we have resolved long-standing uncertainties regarding the formations' depositional ages. Our study thereby provides the first chronostratigraphic framework for these strategically important sedimentary units, significantly advancing understanding of regional Paleozoic geology. Graphical abstract

A hybrid key agreement scheme utilized elliptic curve Diffie-Hellman for IoT based advanced metering environment - Mohammad Kamrul Hasan; Md Mehedi Hasan; Anil Kumar Budati; Shayla Islam; Nurhizam Safie; Fatima Rayan Awad Ahmed; Khairul Azmi Abu Bakar; Nissrein Babiker Mohammed Babiker; Taher M. Ghazal (Earth Science Informatics, 2024)

Green Synthesized Zinc Oxide Nanoparticles Attenuate Acrylamide-Induced Cardiac Injury via Controlling Endoplasmic Reticulum Stress–Associated Apoptosis Through ATF3/CHOP/BCL2 Signaling in Rats - Manal Alosaimi; Yasmina M. Abd-Elhakim; Amany Abdel-Rahman Mohamed; Mohamed M. M. Metwally; Tarek Khamis; Wafa S. Alansari; Areej A. Eskandrani; Walaa M. Essawi; Marwa M. Awad; Rehab A. A. El-Shaer; Sarah Ibrahim; Mohamed A. Nassan; et al. (Biological Trace Element Research, 2024)

Sex comparison of oxidative stress, mitochondrial dysfunction, and apoptosis triggers induced by single-dose Abamectin in albino rats - Hossam El Din H. Abdelhafez; Amr A. Abdallah; Reda K. Abdel-Razik; Nadia A. Hamed; Ahmed Elshatory; Walaa Awad; Abdel Azeim A. Khalaf; Aya M. Mekkawy (Pesticide Biochemistry and Physiology, 2024)

CoFe2O4/PANI/MWCNTs ternary hybrid composites. Synthesis, characterization, the effect of MWCNTs ratio and dye removal capability - Mohamed A. Gabal; Ebtesam Al-Mutairi; Yaser M. Al Angari; Mohamed Abdel Salam; Ayman Awad; Amani A. Al-Juaid; Abdu Saeed (Environmental Science and Pollution Research, 2024)

Intensifying heat using AgCu core-shell-based black titania with highly efficient photothermal conversion performance for solar-driven seawater desalination - Amira Mowafy; Amr Awad Ibrahim; Ahmed Gebreil; Rania M. Eltabey; Awad I. Ahmed; Mina Shawky Adly (Desalination, 2024)

Towards Sustainable Pest Management: Toxicity, Biochemical Effects, and Molecular Docking Analysis of Ocimum basilicum (Lamiaceae) Essential Oil on Agrotis ipsilon and Spodoptera littoralis (Lepidoptera: Noctuidae) - Mona Awad; Nawal Abdulaziz Alfuhaid; Alia Amer; Nancy N. Hassan; Moataz A. M. Moustafa (Neotropical Entomology, 2024)
Over the last decade, essential oils (EOs) have become potential ingredients for insecticide formulations due to their widespread availability and perceived safety. Therefore, this study aimed to evaluate the toxicity and biochemical efficacy of basil ( Ocimum basilicum ) (Lamiaceae) against two destructive pests Noctuidae, Agrotis ipsilon (Hufnagel) and Spodoptera littoralis (Boisduval) (Lepidoptera: Noctuidae). In addition, a molecular docking study was performed to gain insight into the binding pattern between glutathione S-transferase (GST) and linalool, the main component of EO. GC–MS analysis of O. basilicum EO revealed that linalool is the most abundant compound (29.34%). However, the toxicity tests showed no significant difference between the values of LC 50 of O. basilicum EO to A. ipsilon and S. littoralis . On the other hand, the sublethal experiments indicated that treating the second instar larvae with LC 15 or LC 50 values of O. basilicum EO significantly prolonged the larval duration in both insects, compared to the control. Regarding the biochemical effect of O. basilicum EO, the treatments significantly impacted the activity of detoxification enzymes. A notable elevation in glutathione S-transferase (GST) activity was recorded in A. ipsilon larvae compared with a reduction in S. littoralis larvae. The molecular docking analysis revealed that linalool bonded with the amino acid serine (SER 9) of GST, indicating its binding affinity with the enzyme. The obtained results could offer valuable insights into the mode of action of O. basilicum and can encourage the adoption of sustainable pest control practices that incorporate essential oils.

Molecular technology in paleontology and paleobiology: Applications and limitations - Ahmed Awad Abdelhady; Barbara Seuss; Sreepat Jain; Douaa Fathy; Mabrouk Sami; Ahmed Ali; Ahmed Elsheikh; Mohamed S. Ahmed; Ashraf M.T. Elewa; Ali M. Hussain (Quaternary International, 2024)

The Middle-Upper Eocene in the Northern Plateau of the Bahariya Depression, Western Desert (Egypt) and correlation with other Tethyan sectors - Ehab M. Assal; Hamdalla A. Wanas; Heba A. Abou Awad (Marine and Petroleum Geology, 2024)

The Amputated Limb Gluteus Medius is Biomechanically Disadvantaged in Patients with Unilateral Transfemoral Amputation - Galen F. Roda; Mohamed E. Awad; Danielle H. Melton; Cory L. Christiansen; Jason W. Stoneback; Brecca M. M. Gaffney (Annals of Biomedical Engineering, 2024)

Taphonomic damage of molluscan shells in the Nile Delta under natural and anthropogenic sources of environmental variability - Ahmed Awad Abdelhady; Hatem F. Hassan; Basma A.A. Balboul; Khalaf H.M. Abdel-Raheem; Aziz Abu Shama; Mohamed Ahmed; Ali M. Hussain (Journal of African Earth Sciences, 2024)

Characterization of soot emitted from the atmospheric combustion of diethyl ether-diesel blends - Mohammed Ameen Ahmed Qasem; Awad B.S. Alquaity; Usama Ahmed; Eid M. Al-Mutairi; Abdul Gani Abdul Jameel (Fuel, 2024)

Evaluation of the subsurface structural features of the Farafra Oasis, western desert, Egypt using aeromagnetic data - Mohamed M. Khalifa; Waheed H. Mohamed; Mahmoud A. El Ammawy; Ayman I. Taha; Ahmed Awad; Ahmed Awad Orchid (Modeling Earth Systems and Environment, 2024)

Silica-embedded nutrient-doped biochar improves nutrient availability and safflower (Carthamus tinctorius L.) growth in cadmium- and lead-contaminated soil - Munir Ahmad; Hamed Ahmed Al-Swadi; Jahangir Ahmad; Muhammad Usama; Mohammed Awad Mousa; Nahrir M. A. Lubis; Muhammad Imran Rafique; Mohammad I. Al-Wabel; Abdullah S. Al-Farraj (Journal of Soils and Sediments, 2024)

THMs removal from aqueous solution using hydrochar enhanced by chitosan nanoparticles: preparation, characterization, kinetics, equilibrium studies - H. S. Jahin; A. Hesham; Y. M. Awad; S. El-Korashy; G. Khairy (International Journal of Environmental Science and Technology, 2024)
In this study, novel green and economical techniques were established to synthesize modified banana peel hydrochar (HBP) through hydrothermal carbonization. Chitosan nanoparticles, a green adsorbent with multiple features, were prepared, characterized, and used to enhance the performance of the hydrochar in THMs removals. The optimal method for hydrothermal carbonization was determined based on previously cited methods. The dried banana peels and HBP were characterized using Fourier transform infrared spectrometer (FTIR), pH, zero point of charge, and bulk density. The prepared chitosan nanoparticles were characterized using scanning electron microscope (SEM), transmission electron microscope (TEM), and zeta potential techniques. The average size of chitosan nanoparticles was 12.1 nm, and a 1:1 mixture of HBP and chitosan nanoparticles was used for the removal of THMs from an aqueous solution. The concentrations of THMs were measured using gas chromatography, and the effect of THMs’ initial concentrations, adsorbent doses, temperature, and pH value on the adsorption capacity was studied. The results showed that the 1:1 mixture of HBP and chitosan nanoparticles was an efficient adsorbent for removing THMs from aqueous solutions. This adsorbent was found to be effective in removing THMs from the aqueous solution, even at low temperature and pH values, with an estimated maximum sorption capacity ( q m ) of 588.23 g g −1 , exceeding numerous other adsorbents previously studied, and the regression coefficient ( R 2 = 0.9959) for data fitting with the Freundlich isotherm. This research has the potential to offer a great avenue for future development and implementation in water treatment. It could lead to improved methods of treating water, which would be beneficial for both environmental protection and economic growth. The developed adsorbent had high adsorption affinity toward the THMs compounds, making the adsorption method efficient and viable technique for treating water containing such contaminants.

Ameliorative effect of montelukast against STZ induced diabetic nephropathy: targeting HMGB1, TLR4, NF-κB, NLRP3 inflammasome, and autophagy pathways - Ahmed M. Awad; Sally L. Elshaer; Rajashekhar Gangaraju; Rania R. Abdelaziz; Manar A. Nader (Inflammopharmacology, 2024)
Diabetic nephropathy (DN) is reported as one of the most serious microvascular diabetic complications and the trigger of end-stage renal disease (ESRD), underscoring the concern of any therapeutic intervention directed at ameliorating the development and progression of DN. The current study explored the renoprotective impact of montelukast (Mon) against streptozotocin (STZ)-induced DN in rats compared to a standard anti-hyperglycemic insulin (Ins) treatment. Diabetes was induced by a single dose of STZ (55 mg/kg). Diabetic rats were treated with Mon (10 and 20 mg/kg, oral gavage) for eight weeks. Mon administration for 8 weeks after induction of diabetes conferred significant dose-dependent renoprotection, independent of blood glucose levels (unlike Ins), as evidenced by the improvement in serum creatinine, and blood urea nitrogen (BUN), and ameliorated STZ-induced renal necrotic, inflammatory alterations, and renal fibrosis. Additionally, Mon treatment in diabetic rats significantly restored redox hemostasis as evidenced by malondialdehyde (MDA) and total antioxidant capacity (TAC) levels; significantly reduced the renal expression of high mobility group box (HMGB) 1, toll-like receptor (TLR) 4, nuclear factor kappa B (NF-κB) (in the nucleus), NOD-like receptor family pyrin domain containing (NLRP) 3, and interleukin (IL)-1β. Moreover, Mon administration ameliorated the dysregulation in autophagy as evidenced by p62 and microtubule-associated protein 1A/1B-light chain 3 (LC3)-II levels. In conclusion, the renoprotective effect of Mon is potentially associated with its modulatory effect on inflammatory cytokines, antioxidant properties, and autophagy. Graphical Abstract Renoprotective effect of montelukast and its underlying pathway: Hyperglycemia and advanced glycation end products (AGEs) stimulate the release of high mobility group box (HMGB) 1 from necrotic and inflammatory cells. HMGB1 is considered as one of the endogenous ligands of toll-like receptor (TLR) 4, and the interaction of HMGB1 with TLR4 results in a subsequent translocation of nuclear factor kappa B (NF-κB) from the cytoplasm into the nucleus inducing an inflammatory response. NF-κB is a key mediator of the priming signal responsible for the activation of NOD-like receptor family pyrin domain containing (NLRP) 3 inflammasome by stimulating the expression of both NLRP3 and pro- interleukin (IL)-1β, which is then converted to IL-1β by to mediate inflammation. NLRP3 can induce reactive oxygen species production, while autophagy inhibits AGEs and NLRP3 accumulation. Montelukast show an inhibitory effect on HMGB1, TLR4, NF-κB, NLRP3, and IL-1β and has autophagy stimulating characteristics indicating its potential renoprotective effect.

The puzzling etiologies of transient black discoloration in Nile Tilapia (Oreochromis niloticus) intensively cultured under RAS system - Alaa Eldin Eissa; Marwa M. Attia; Rabia A. El Zlitne; Ayad A. Magdy; Asmaa Edrees; Mahmoud S. Sharaf; Abeer E. Mahmoud; Awad A. Abdelbaky; Rehab R. Abd ElMaged; Elshaimaa Ismael; Rehab A. Qorany; Doaa F. El Moghazi; et al. (Aquaculture International, 2024)
The aim of this study is to identify the hidden etiologies of the black chromo-shifting transient phenomenon affecting Nile tilapia, Oreochromis niloticus , farmed in RAS-controlled ponds together with the assessment of the immunological reaction against the chronic irritating effects of the invasive agent. A total of 100 Nile Tilapia were collected from a private farm at Kafrelsheikh Province, located on the northern side of the Egyptian Nile Delta. The clinical history of the affected fish farm showed an unknown chromo-shifting phenomenon where tilapias were exhibiting severe black skin coloration, which gradually disappeared after removal from the tank’s water. A comprehensive gross examination of the collected fish; including parasitological examination of skin and gill scraps, was performed. Blood biochemical testing was performed on the infested blackish O. niloticus and control non-infested fish. The current study showed that the monogenean parasite, Gyrodactylus cichlidarum , was the abundant parasite detected in the infested fish leading to abnormal black discoloration of skin and disruption of the immune system represented by significant increase of cortisol levels, lysozyme activity and different liver enzymes compared to the control. Treatment trials have been applied with moderate degrees of success, where the monogenean count was sharply decreased, and the normal skin color was remarkably restored, at the end of day 14 post-treatment. A triple treatment plan was initiated through 7 days’ application of 0.7 g/m 3 copper sulfates pentahydrate preceded by 1.5 ml/m 3 hydrogen peroxide 40% solution for the same period. One day after the end of the initial treatment, a maintenance dosage of 0.095 ml/m 3 of glutaraldehyde (15%)/quaternary ammonium compounds (QACs) mixture was administered for 3 days. As a supportive/immune-stimulant regimen, a weekly dosage of vitamin C (0.45 g g/m 3 ) and Saccharomyces cerevisiae (0.45 g/m 3 ) was added into the tank’s water to improve the general fish health.

Truths and myths about superfoods in the era of the COVID-19 pandemic - Abdo Hassoun; Rania Harastani; Sandeep Jagtap; Hana Trollman; Guillermo Garcia-Garcia; Nour M. H. Awad; Oscar Zannou; Charis M. Galanakis; Gulden Goksen; Gulzar Ahmad Nayik; Asad Riaz; Sajid Maqsood (Critical Reviews in Food Science and Nutrition, 2024)

Preparation and evaluation of ecofriendly nanocreams containing some plant essential oils and monoterpenes against adults of Culex pipiens L. with some biochemical and histological studies on albino rat - Nehad E. M. Taktak; Mohamed E. I. Badawy; Osama M. Awad; Nadia E. Abou El-Ela; Samar M. Aborhyem (International Journal of Tropical Insect Science, 2024)
Plant essential oils (EOs) are considered a vital tool of novel natural mosquito repellents and botanical adulticides. Five plant EOs (cinnamon, cypress, lavender, lemon eucalyptus and tea tree) and their major constituents (cinnamaldehyde, citronellal, β-cymene, (R)-linalool, and α-terpinyl acetate) were investigated against adults of Culex pipiens . The efficacy of the tested compounds was manipulated as mortality and knockdown using a fumigation technique. After that, the most active compounds against adults (lemon eucalyptus oil and linalool) were investigated once more as repellents after incorporating them on a cream base against C. pipiens adults compared to their nano-cream using arm-in-cage technique. In addition, the biochemical and histological effects of dermal treatment of linalool, lemon eucalyptus,, and their nanoemulsions (NEs) were studied on male albino rats. Total protein assay, acetylcholinesterase (AChE), adenosine triphosphatase (ATPase), and liver and kidney functions were determined in blood serum. Complete blood count (CBC) was determined in whole blood. The results showed that lemon eucalyptus oil and (R)-linalool caused the highest knockdown activity against C. pipiens adults with Kt 50 40.29 s and 12.73 s, respectively. The repellent effect (RC 50 ) of nanocream formulations of lemon eucalyptus oil (10.03 mg/L) and (R)-linalool (68.11 mg/L) were higher than the original effects of these compounds with RC 50 values = 100.82 mg/L and 998.54 mg/L, respectively. There are no obvious harmful side effects of the dermal topical treatments of (R)-linalool and lemon eucalyptus oil on the tested biochemical parameters of treated albino rats compared with the control. Furthermore, there are no obvious effects of the dermal topical treatments of (R)-linalool and lemon eucalyptus oil on the histological status of the treated skin of albino rats compared with untreated treatment. The tested oils and monoterpenes could be considered promising candidates for botanical adulticides against C. pipiens . Also, nano-cream of lemon eucalyptus oil and (R)-linalool could be considered promising ecofriendly repellents for C. pipiens adults.

Exergy and energy analysis of a novel solar powered fog desalination system - Ahmed E. Abu El-Maaty; Mohamed M. Awad; Bilal A. Qureshi (Desalination, 2024)

Ecofriendly synthesis and nematicidal application of copper nanoparticles fabricated from Bacillus subtilis AM18, against root-knot nematode of cucumber - Ramadan M. El-Ashry; Maha M. Nader; Ashwag Shami; Manal A. Alduwish; Ahmed Ezzat Ahmed; Soha A. Alamoud; Aminah Allohibi; Fatimah S. Alqahtani; Amira M. Alghamdi; Alshaymaa I. Ahmed; Mokhles A. A. Hassan; Salonaz E. Awad; et al. (European Journal of Plant Pathology, 2024)

Evaluating the protective role of trimetazidine versus nano-trimetazidine in amelioration of bilateral renal ischemia/reperfusion induced neuro-degeneration: Implications of ERK1/2, JNK and Galectin-3 /NF-κB/TNF-α/HMGB-1 signaling - Fatma E. Hassan; Basma Emad Aboulhoda; Isra H. Ali; Heba M. Elwi; Lamiaa M. Matter; Hend Ahmed Abdallah; Mohamed Mansour Khalifa; Asmaa Selmy; Mansour A. Alghamdi; Suzan Awad Morsy; Basant A. Al Dreny (Tissue and Cell, 2023)

Upper Cretaceous (Coniacian-Santonian) low diversity oyster-dominated macrofaunal association in the Eastern Desert of Egypt: Taphonomy versus ecology - Ahmed Awad Abdelhady; Wagih Ayoub-Hannaa; Mohamed S. Ahmed; Ali M. Hussain (Journal of African Earth Sciences, 2023)

Evaluating Mesh Geometry and Shade Coefficient for Fog Harvesting Collectors - Abdullah A. Elshennawy; Magdy Y. Abdelaal; Ahmed M. Hamed; Mohamed M. Awad (Water Resources Management, 2023)
The most valuable resource for sustaining life on earth is water. In dry and semi-arid areas, the problem of water scarcity can be resolved with the aid of fog collection techniques employing fog collectors. Fog collection is greatly influenced by a variety of factors. Some are design parameters, while others depend on ambient circumstances. Geometry and the mesh’s shade coefficient are important design factors that can be modified and have an impact on the rate at which fog collects in fog collectors. The shape of the mesh holes and the process used to create the mesh serve to identify geometry and measure the shade coefficient. In this paper, a straightforward mathematical technique is proposed to make it easier to calculate the shade coefficient of various mesh shapes used in fog harvesting and to provide an approximation of the mesh volume and cost. Five alternative geometries were used: the rectangular mesh, square mesh, Raschel mesh, triangular mesh, and hexagonal mesh. The current simple method will facilitate the design of the fog mesh collector and can assist in achieving the ideal shade coefficient and most effective mesh geometry for fog harvesting. Rectangular meshes were solely used as an example to evaluate the results. Stainless steel rectangular meshes with various shade coefficients were tested for fog collection, and the amount of water collected by each mesh varied. It was concluded that the optimum shade coefficient ranged 50–60% for fog collection.

Brief report first report of the in vitro ovicidal activity of camel milk and its fractions on zoonotic-liver fluke (Fasciola gigantica) eggs - Dina A.B. Awad; Amany S. Eldiarby; Mona Abdallah; Ahmed Hamad; Samah M. Abdel Gawad (Veterinary Research Communications, 2023)
Fasciola gigantica is one of the worldwide parasites that cause livestock and human illnesses. Chemotherapy is now the primary therapeutic option for its treatment. Drug abuse has led to the emergence of drug-resistant strains. As a result, there is an urgent need to discover natural and efficient anthelmintics against Fasciola spp. The study aims to evaluate the ovicidal activities of camel milk and its fractions on F. gigantica eggs. In the in vitro assay of F. gigantica eggs were submitted to different concentrations (0.5% and 1%) of camel milk fractions; Camel Milk Whey (CMW), Camel Milk Casein (CMC), and Skimmed Camel Milk (SCM) as well as a positive control (PC) of Nitroxynil (100 mg/ml) and a negative control (NC) with physiological saline. The Egg Hatching Assay (EHA) results showed that camel milk fractions exhibited ovicidal activity, especially CMW, and CMC, which showed 97.58 ± 0.58 and 96.9 ± 1.99 ovicidal activity, respectively, at a concentration of 1% after 15 days of treatment compared to PC, which exhibited 91.75 ± 4.95 ovicidal activity. The egg hatching ratios were 1.67% and 2.33% for CMW and CMC, respectively, compared to 70.17% for the NC and 6% for the PC. The LC 50 values for CMW and CMC on the 15th day of treatment were 0.20 and 9.13, respectively. From the results above, we can infer that camel milk and its fractions are promising as a new alternative for fascioliasis control.

Exogenous Application of Silicon and Sulfate Improved Drought Tolerance in Sunflowers Through Modulation of Morpho-physiological and Antioxidant Defense Mechanisms - Muhammad Nisar; Muhammad Aqeel; Abdul Sattar; Ahmad Sher; Muhammad Ijaz; Sami Ul-Allah; Umair Rasheed; Salem Mesfir Al-Qahtani; Nadi Awad Al-Harbi; Fahad Mohammed Alzuaibr; Mohamed F. M. Ibrahim (Journal of Soil Science and Plant Nutrition, 2023)

Thermal-Hydraulic modelling and analysis of VVER-1200 reactor core - Salah El-Din El-Morshedy; Mostafa M. Awad; Mohamed Abo El-Fetouh (Annals of Nuclear Energy, 2023)

Climatology of the spring subtropical jet stream over the Middle East and its effect on the synoptic characteristics of dust systems over the northern Arabian Peninsula - Yazeed H. Alsubhi; Adel M. Awad; Abdul-Wahab S. Mashat; Abdulhaleem H. Labban (Arabian Journal of Geosciences, 2023)

Synergistic effect of β-sitosterol and biochar application for improving plant growth of Thymus vulgaris under heat stress - Khadiga Alharbi; Amir Abdullah Khan; Haifa Abdulaziz Sakit Alhaithloul; Nadi Awad Al-Harbi; Salem Mesfir Al-Qahtani; Saeedah Sallum Aloufi; Awatif M. Abdulmajeed; Muhammad Atif Muneer; Suliman M.S. Alghanem; Muhammad Zia-ur-Rehman; Muhammad Usman; Mona H. Soliman (Chemosphere, 2023)

Evaluating the effect of Spirulina platensis on the immune response of broiler chickens to various vaccines and virulent Newcastle disease virus challenge - Ashraf M. Awad; Mahmoud E. Sedeik; Ahmed H. Salaheldin; Raghda I. Goda; Nahed A. El-Shall (Research in Veterinary Science, 2023)

Growth patterns of Pseudomonas aeruginosa in milk fortified with chitosan and selenium nanoparticles during refrigerated storage - Rehab M. Atia; Hamdi A. Mohamed; Nahla A. AboELRoos; Dina A. B. Awad (World Journal of Microbiology and Biotechnology, 2023)
Pseudomonas spp are considered a common milk-associated psychotropic bacteria, leading to milk deterioration during storage; therefore, our study aimed to study the distribution of Pseudomonas aeruginosa in raw milk and its associated products then studying the growth behavior of P. aeruginosa in milk after employing chitosan nanoparticles (CsNPs 50, 25, and 15 mg/100ml) and selenium nanoparticles (SeNPs 0.5, 0.3 and 0.1 mg/100ml) as a trial to control the bacterial growth in milk during five days of cooling storage. Our study relies on the ion gelation method and green synthesis for the conversion of chitosan and selenium to nanosized particles respectively, we subsequently confirmed their shape using SEM and TEM. We employing Pseudomonas selective agar medium for monitoring the bacterial growth along the cooling storage. Our findings reported that high prevalence of Pseudomonas spp count in raw milk and kareish cheese and high incidence percent of P. aeruginosa in ice cream and yogurt respectively. Both synthesized nanoparticles exhibited antibacterial activity in a dose-dependent manner. Moreover, CsNPs50 could inhibit the P. aeruginosa survival growth to a mean average of 2.62 ± 1.18 log 10 cfu/ml in the fifth day of milk cooling storage; also, it was noted that the hexagonal particles SeNPs0.5 could inhibit 2.49 ± 11 log 10 cfu/ml in comparison to the control P. aeruginosa milk group exhibited growth survival rate 7.24 ± 2.57 log 10 cfu/ml under the same conditions. In conclusion, we suggest employing chitosan and selenium nanoparticles to improve milk safety and recommend future studies for the fate of nanoparticles in milk.

Synthesis, antiproliferative activity, and molecular modeling of novel 4-methylcoumarin derivatives and/or nitric oxide donor hybrids - Malik Suliman Mohamed; Hany A. M. Elsherief; Hani Mohamed Hafez; Omar Awad Alsaidan; Samil I. Alzarea; Asmaa M. AboulMagd (Molecular Diversity, 2023)

Exploring the potential of quercetin/aspirin-loaded chitosan nanoparticles coated with Eudragit L100 in the treatment of induced-colorectal cancer in rats - Mohammed Elmowafy; Khaled Shalaby; Mohammed H. Elkomy; Omar Awad Alsaidan; Hesham A. M. Gomaa; Omnia M. Hendawy; Mohamed A. Abdelgawad; Hazim M. Ali; Yasmin M. Ahmed; Khalid M. El-Say (Drug Delivery and Translational Research, 2023)

Effects of dietary nano-selenium supplementation on Riemerella anatipestifer vaccinated and challenged Pekin ducklings (Anas platyrhynchos) - Abdelfattah H. Eladl; Nehal M. Nabil; Amal Awad; Shereen Badr; Amera F. Ebrahem; Maram M. Tawakol; Enas Hammad; Hanaa S. Ali; Reham A. El-Shafei (Veterinary Microbiology, 2023)

Comparable bio-evaluation of curcumin and chitosan-encapsulated curcumin nanoparticles against the reprotoxic potential of fenpropathrin pyrethroid in rats: Genomic and morphometric prospectives - Amany Abdel-Rahman Mohamed; Amany Behairy; Yasmina M. Abd El-Hakim; Mohamed M.M. Metwally; Tarek Khamis; Samah S. Abuzahrah; Ahmed E. Abdelhamid; Leena S. Alqahtani; Walaa M. Essawi; Badriyah S. Alotaibi; Manal Alosaimi; Rehab Ahmed Ahmed El-Shaer; et al. (Food and Chemical Toxicology, 2023)

Effect of potential microplastics in sewage effluent on Nile Tilapia and photocatalytic remediation with zinc oxide nanoparticles - Manal Qayyadh Alanazi; Promy Virk; Seham Soliman Alterary; Manal Awad; Zubair Ahmad; Abdulrehman M. Albadri; KalidM. Ortashi; Mohieldeen Mahgoub A. Ahmed; Mohamed Ismail Ali Yousef; Mai Elobeid; Ebtesam Abdullah Al-Qahtani (Environmental Pollution, 2023)

Melatonin Mitigates Salt-Induced Growth Inhibition Through the Regulation of Carbohydrate and Nitrogen Metabolism in Tomato Seedlings - Mohammad Shah Jahan; Guihua Li; Dasen Xie; Reham Farag; Md. Mahadi Hasan; Nadiyah M. Alabdallah; Nadi Awad Al-Harbi; Salem Mesfir Al-Qahtani; Muhammad Zeeshan; Jamal Nasar; Muhammad Ahsan Altaf; Md Atikur Rahman (Journal of Soil Science and Plant Nutrition, 2023)

Phytochemical analysis and determination of antioxidant, anti-cholesterol, anti-inflammatory and anti-proliferative activities of Gerbera jamesonii flowers - Shaimaa Negm El-Dein; Amal Hussein; Marwa S. Abu-Bakr; Asmaa Negm El-Dein; Hanem M. Awad; Ehab A. Ragab (Advances in Traditional Medicine, 2023)

The Middle-Upper Eocene benthic foraminifera from north-west Fayoum area, Egypt: Paleoecology and their similarity to the Tethyan provinces - Sherif M. El Baz; Hamdalla A. Wanas; Heba Allah Abou Awad; Ehab M. Assal (Journal of African Earth Sciences, 2023)

Ag@Sidr honey nanocomposite: Chemical profiles, antioxidant and microbicide procurator - Nehal Eid; Nermeen Yosri; Hesham R. El-Seedi; Hassan M. Awad; Hossam E. Emam (Biocatalysis and Agricultural Biotechnology, 2023)

Correction to: Dephenolization and discoloration of olive mill wastewater using coagulation, filtration, and hydrogen peroxide oxidation - M. A. Al-Shaweesh; A. Awad; D. Al-Kabariti; M. S. Al-Hwaiti; Omar A. Al-Khashman; A. F. Khafaga; M. E. Abd El-Hack; F. A. Adday (International Journal of Environmental Science and Technology, 2023)

Dephenolization and discoloration of olive mill wastewater using coagulation, filtration, and hydrogen peroxide oxidation - M. A. Al-Shaweesh; A. Awad; D. Al-Kabariti; M. S. Al-Hwaiti; O. A. Al-Kashman; A. F. Khafaga; M. E. Abd El-Hack; F. A. Adday (International Journal of Environmental Science and Technology, 2023)

Ni-Cu bimetallic catalytic membranes for continuous nitrophenol conversion - Nan Zhang; Yichen Wu; Abdelrahman M. Awad; Emmanuel Doelsch; Charles-François de Lannoy (Chemical Engineering Journal, 2023)

Microfoundations of the waste-to-resource problem in circular economy transitions: Antenarratives of phosphorus in Dutch agribusiness (2008–2014) - M. Hassan Awad (Journal of Cleaner Production, 2023)

Corrigendum to “Prasugrel anti-ischemic effect in rats: Modulation of hippocampal SUMO2/3-IкBα/Ubc9 and SIRT-1/miR-22 trajectories” [Toxicol Appl Pharmacol. 2021 Sep 1;426:115635] - Asmaa A. Gomaa; Hanan S. El-Abhar; Dalaal M. Abdallah; Azza S. Awad; Ayman A. Soubh (Toxicology and Applied Pharmacology, 2023)

Novel control of house fly Musca domestica and bacterial isolates by ozone gas - Ahmed M. Metwally; Salem S. Salem; Kotb M. Hammad; Khaled H. Metwaly; Mohamed A. Awad (International Journal of Tropical Insect Science, 2023)
Ozone is a sturdy oxidant which canrub insects and microorganisms. Thus, it could be useful in eliminate the Housefly in hospitals. The purpose of test here is to determine degree of ozone exposure required to remove houseflies and reduction of pathogenic bacteria. Ozone was effective with housefly, requiring only low minutes of treatment (1 to 14 min.) at minimum concentrations of ozone gas O 3 (0.125 g/m 3 to 1 g/m 3 ), the insects were eliminated the ozone. Thus, ozone exhibit potential as a fumigant for ousefly nesting materials, but moreover research is needed to evaluate its acceptability and efficacy in that field. The need for a dependable method to decontaminate housefly nesting materials as part of an overall ousefly ( Musca domestica ) system at hospitals sterilization is discussed. In this paper, we are using ozone gas as an alternative housefly pest and to remove house flies at hospitals, and we also illustrate data on the efficacy of ozone against the housefly ( Musca domestica ) and its effect on specific characteristics and properties of the treated zone application is currently attracting attention, particularly since. (a) There are no residues on the product. (b) There is no need for aeration to remove the gas. Green synthesis industrial applications and improvements in ozone technology together with new regulatory actions worldwide have emerged in last years, making it easier to use and applicable in a wide range - as the same with the pathogenic bacteria we are using ozone gas to control it, the numbers of bacterial cells remaining after ozone treatments were less than for untreated cells. The lowest dose of ozone gas for complete reduction of pathogenic bacteria was 0.125 g/m 3 after 24 h of incubation.

Fe-Co spinel oxides supported UiO-66-NH2 derived zirconia/ N-dopped porous hollow carbon as an efficient oxygen reduction reaction electrocatalyst - Soliman Gamal; Doaa A. Kospa; Mahmoud M. Kaid; S.A. El-Hakam; Awad I. Ahmed; Amr Awad Ibrahim (Journal of Environmental Chemical Engineering, 2023)

Suppression of Meloiodogyne incognita (Tylenchida: Heteroderidae) and Tylenchulus semipenterans (Tylenchida: Tylenchulidae) using Tilapia fish powder and plant growth promoting rhizobacteria in vivo and in vitro - Ramadan M. El-Ashry; Ahmed A. A. Aioub; Salonaz E. Awad (European Journal of Plant Pathology, 2023)
Plant-parasitic nematodes (PPNs) in particular those belonging to the genera Meloidogyne and Tylenchulus are a limiting factor in the production of many plants. In this research, we investigate a strategy for the control of PPNs in vivo and in vitro. The purpose of this research is to evaluate different concentrations of Tilapia fish powder (TFP) and of (in the form of BECTO Grow Roots®) against egg hatching and second-stage juveniles of Meloiodogyne incognita (Tylenchida: Heteroderidae) under laboratory condition. We also assessed the effect of TFP and on M. incognita and Tylenchulus semipenterans (Tylenchida: Tylenchulidae) reproduction. Our data showed that the percentage of egg hatching inhibition ranged from 8.03 to 53.21% and 42.25 to 75.12% after five days of treatment at different concentrations of TFP and PGPR, respectively compared with the control. The percentage of M. incognita J2 mortality increase significantly ( p ≤ 0.05) from 52.1 to 86.7 and 44.6 to 92.3% after seven days of treatment at different concentrations of TFP and PGPR, respectively compared with control. Under greenhouse conditions, a remarkable ( p ≤ 0.05) increase in plant growth parameters was observed in cucumber plants that received TFP and In the field experiment, the highest reduction of T. semipeneterans density was TFP + PGPR This holds both for healthy and infected trees. Healthy navel orange (HNO) + PGPR + TFP achieved maximum enhancement in orange weight/tree compared to other treatments. Our study recommended TFP and PGPR not only because of their potential against nematodes, but also because of their safety for humans, mammals and non-target organisms.

Efficacy of cryotherapy combined with intralesional purified protein derivative (PPD) versus intralesional PPD monotherapy in the treatment of multiple common warts - Sara M. Awad; Ahmed S. Gomaa; Hiba A.H. Abdullah; Yasmin M. Tawfik (Cryobiology, 2023)

Magnetic Signature of Gold Deposits: Example from Um Garayat Region, South Eastern Desert, Egypt - Mohamed Mostafa Gobashy; Mahmoud M. Mekkawi; Sultan Awad Sultan Araffa; Moahmed M. Ezz Eldin; Mohamed Hassan Khalil (Pure and Applied Geophysics, 2023)
Magnetic methods of exploration have proved to be efficient and have potential in the gold mineralization industry. New magnetic processing technologies aid in improving the process of interpretation and gold opportunity identification. In this work, we show the possible application of combined digital magnetic filters to explore new gold mineralization localities with application to a well-known Au mineralization zone. Um Garayat (UG) region, southeastern desert, Egypt, is an ancient example of a potential area for gold mining. Modern analysis showed that other types of mineral concentrations are present. So, exploiting the magnetic signature of the area for future investment is of great interest. The old UG gold mine is characterized by volcanic and tectonic features such as faulting and folding that affect the arc sedimentary rock sequence of repeated deformation stages. A thorough geophysical effort has been carried out around the old gold mine in the UG area to explore the extension of mineralized ore deposits. A detailed geophysical survey using magnetics was carried out in this study together with the available aeromagnetic data. Field data sets on appropriate sites were measured, processed, and evaluated by suitable software. High magnetic anomalies were detected based on grid filter analysis and contact occurrence maps as marked as possible ore deposits after satisfying the geologic conditions for gold formation. An integrated understanding of attained results revealed that the new possible ore deposits are related directly to fault and fracture zones in the shape of lenses of variable thickness in this zone. Results show that newly detected mineral occurrences in the UG area are also controlled by major faults and hydrothermal solution enrichment along fault zones at a depth ranging from 20 to 70 m. Favorable fault/joint mineralized places were located. The relationship between the Au-quartz vein's strike direction compared with magnetic anomaly lineament analysis was studied. Search for new sources of Au and other mineral deposits in addition to quartz veins is needed as pockets of accumulated mineral-rich rock fragments are deposited in drainage wadis and fault/joint zones because of hydrothermal solution enrichment.

Bioactive compounds, pharmacological actions and pharmacokinetics of Cupressus sempervirens - Gaber El-Saber Batiha; John Oluwafemi Teibo; Hazem M. Shaheen; Opeyemi Abigail Akinfe; Aya Ahmed Awad; Titilade Kehinde Ayandeyi Teibo; Athanasios Alexiou; Marios Papadakis (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)
The roles of plants and its products in all forms of life cannot be overemphasized. The medicinal products from plant are phytochemicals, drugs, food supplements, beauty products, etc. In ethnomedicine, leaves, fruits, stem, bark, root and fluids from plants are used in the cure, management and prevention of several diseases. Cupressus sempervirens , sometimes called Italian or Mediterranean cypress, is found in subtropical Asia, North America and eastern Mediterranean region. Pharmacological investigations of Cupressus sempervirens showed biological properties such as aromatherapeutic, antiseptic, astringent, balsamic or anti-inflammatory, astringent, antiperspirant, diuretic and antispasmodic. Chemical analysis of Cupressus sempervirens gives phytochemicals like monoterpenes, diterpenes, flavonoid glycosides and bioflavonoids. The current review highlights interactions, conventional uses and biological actions of Cupressus sempervirens plant and plant products.

Carbohydrate microcapsules tailored and grafted for covalent immobilization of glucose isomerase for pharmaceutical and food industries - Mohamed E. Hassan; Ghada E. A. Awad; Mohamed S. MohyEldin; Bakry M. Haroun; Ahmed I. El-Diwany; Magdy M. Elnashar (Biotechnology Letters, 2023)

Combined Effect of Biochar and Salicylic Acid in Alleviating Heavy Metal Stress, Antioxidant Enhancement, and Chinese Mustard Growth in a Contaminated Soil - Mahrous Awad; Mohamed Moustafa-Farag; Zhongzhen Liu; Rasha M. El-Shazoly (Journal of Soil Science and Plant Nutrition, 2022)

Soil and foliar applications of zinc sulfate and iron sulfate alleviate the destructive impacts of drought stress in wheat - Md. Abdul Mannan; Mahmuda Akter Tithi; M. Rafiqul Islam; Md. Abdullah Al Mamun; Shamim Mia; Md. Zillur Rahman; Mohamed F. Awad; Abdelaleim I. ElSayed; Elsayed Mansour; Md. Sazzad Hossain (Cereal Research Communications, 2022)

Prophylactic and curative effects of Carica papaya Linn. pulp extract against carbon tetrachloride-induced hepatotoxicity in male rats - Nadia Zaki Shaban; Olfat M. Awad; Ghada M. Fouad; Afaf M. Hafez; Ahmed Alaa Abdul-Aziz; Sarah M. El-Kot (Environmental Science and Pollution Research, 2022)
Several chemicals and medications induce cellular damage in various organs of the body by activating reactive substances’ metabolism leading to various pathological conditions including liver disease. In this study, we evaluated the prophylactic and curative effects of Carica papaya Linn . pulp water extract (PE) against CCl 4 -induced rat hepatotoxicity. Five groups of rats were created, control, PE, CCl 4 , (PE-CCl 4 ): The rats were administered with PE pre and during CCl 4 injection, and (PE-CCl 4 -PE): The rats were administered with PE pre, during, and after CCl 4 . The markers of oxidative stress (“OS”: oxidant and antioxidants), inflammation [nuclear factor-κB, tumor necrosis factor-α, and interleukin-6], fibrosis [transforming growth factor-β], and apoptosis [tumor suppressor gene (p53)] were evaluated. Additionally, liver functions, liver histology, and kidney functions were measured. Also, PE characterization was studied. The results showed that PE, in vitro, has a high antioxidant capacity because of the existence of phenolics, flavonoids, tannins, terpenoids, and minerals. Otherwise, the PE administration [groups (PE-CCl 4 ) and (PE-CCl 4 -PE)] exhibited its prophylactic and therapeutic role versus the hepatotoxicity induced by CCl 4 where PE treatment improved liver functions, liver histopathology, and renal functions by decreasing oxidative stress, inflammation, fibrosis, and apoptosis induced by CCl 4 . Our study elucidated that PE contains high amounts of phenolics, flavonoids, tannins, terpenoids, and ascorbic acid. So, PE exerted significant prophylactic and curative effects against hepatotoxicity induced by CCl 4 . These were done by enhancing the markers of antioxidants and drug-metabolizing enzymes with reductions in lipid peroxidation, inflammation, fibrosis, and apoptosis. PE administration for healthful rats for 12 weeks had no negative impacts. Consequently, PE is a promising agent for the prohibition and therapy of the toxicity caused by xenobiotics.

Influence of COVID-19 on the sustainability of livestock performance and welfare on a global scale - Md. Tanvir Rahman; Md. Saiful Islam; Awad A. Shehata; Shereen Basiouni; Hafez M. Hafez; Esam I. Azhar; Asmaa F. Khafaga; Fulvia Bovera; Youssef A. Attia (Tropical Animal Health and Production, 2022)

Synthesis and in silico evaluation of novel uridyl sulfamoylbenzoate derivatives as potential anticancer agents targeting M1 subunit of human ribonucleotide reductase (hRRM1) - Prince J. Salvador; Heather B. Jacobs; Lujain Alnouri; Asia Fee; Lynn M. Utley; Madison Mabry; Hannah Krajeck; Christopher Dicksion; Ahmed M. Awad (Medicinal Chemistry Research, 2022)

The diagnostic accuracy of intraoperative frozen section biopsy for diagnosis of sentinel lymph node metastasis in breast cancer patients: a meta-analysis - Alaa Ahmed Elshanbary; Alaa Abdelsameia Awad; Alaa Abdelsalam; Islam H. Ibrahim; Walid Abdel-Aziz; Youssef Bahaaeldin Darwish; Alaa Saad Isa; Boutheyna Drid; Marwa Gamal Mustafa; Radwa Hamdy Allam; Amira A. Abo Ali; Anas Zakarya Nourelden; et al. (Environmental Science and Pollution Research, 2022)
Sentinel lymph node (SLN) sampling is important for evaluating the nodal stage of breast cancer when the axillary nodes are clinically free of metastasis. The intraoperative frozen section (IFS) of SLN is used for lymph node assessment. This meta-analysis aims to provide evidence about the diagnostic accuracy and the applicability of IFS of SLN in breast cancer patients. Data were collected by searching PubMed, Cochrane, Scopus, and Web of Science electronic databases for trials matching our eligibility criteria. The statistical analysis included the sensitivity, specificity, positive likelihood ratio, negative likelihood ratio, and pooled studies’ diagnostic odds ratio outcomes. The analyses were conducted using the Open Meta-analyst software. This meta-analysis pooled the results of 110 studies. The overall sensitivity of IFS for SLN metastasis was 74.7%; 95% CI [72.0, 77.2], P < 0.001. It was 31.4% 95% CI [25.2, 38.3], P < 0.001 for the micro-metastasis, and 90.2%; 95% CI [86.5, 93.0], P < 0.001 for the macro-metastasis. The overall specificity was 99.4%; 95% CI [99.2, 99.6], P < 0.001. The overall positive likelihood ratio was 121.4; 95% CI [87.9, 167.6], P < 0.001, and the overall negative likelihood ratio was 0.226; 95% CI [0.186, 0.274], P < 0.001. The overall diagnostic odds ratio of IFS for diagnosing SLN metastasis was 569.5; 95% CI [404.2, 802.4], P < 0.001. The intraoperative frozen section of SLN has good sensitivity for diagnosing breast cancer macro-metastasis. However, the sensitivity is low for micro-metastasis. The specificity is very satisfactory.

Evaluation of Nonparametric Machine-Learning Algorithms for an Optimal Crop Classification Using Big Data Reduction Strategy - B. Al-Awar; M. M. Awad; L. Jarlan; D. Courault (Remote Sensing in Earth Systems Sciences, 2022)

Anticancer activity of chicken cathelicidin peptides against different types of cancer - Maged Mostafa Mahmoud; Modhi Alenezi; Ahmed M. Al-Hejin; Turki S. Abujamel; Fadwa Aljoud; Abdulwahab Noorwali; Ibrahim A. Awad; Mohammed Alkhaled; Haitham A. Yacoub (Molecular Biology Reports, 2022)

Solar photo-oxidation of recalcitrant industrial wastewater: a review - Ahmed Tawfik; Mohamed Gar Alalm; Hanem M. Awad; Muhammad Islam; Muhammad Abdul Qyyum; Ala’a H. Al-Muhtaseb; Ahmed I. Osman; Moonyong Lee (Environmental Chemistry Letters, 2022)
Conventional methods to clean wastewater actually lead to incomplete treatments, calling for advanced technologies to degrade recalcitrant pollutants. Herein we review solar photo-oxidation to degrade the recalcitrant contaminants in industrial wastewater, with focus on photocatalysts, reactor design and the photo-Fenton process. We discuss limitations due to low visible-light absorption, catalyst collection and reusability, and production of toxic by-products. Photodegradation of refractory organics by solar light is controlled by pH, photocatalyst composition and bandgap, pollutant properties and concentration, irradiation type and intensity, catalyst loading, and the water matrix.

Joined Efficiency and Productivity Evaluation of Tunisian Commercial Seaports Using DEA-Based Approaches - Mohsen Ben Mabrouk; Manel Elmsalmi; Awad M. Aljuaid; Wafik Hachicha; Sami Hammami (Journal of Marine Science and Engineering, 2022)
Seaports are important infrastructures to support international trade. Therefore, it is vital that port efficiency and productivity are continuously evaluated and improved. In this context, the objective of this article is to evaluate both the technical efficiency and the change in productivity of the six most important Tunisian commercial seaports, Bizerte, Rades, Sousse, Sfax, Gabes, and Zarzis, over a period of twelve years from 2005 to 2016. To achieve this objective, the data envelopment analysis (DEA) method is applied. The first output-oriented DEA application is about efficiency evaluation, which, for each seaport, allows the estimation of overall technical efficiency, pure technical efficiency, and scale efficiency. The second application concerns the evolution of the productivity of Tunisian seaports during the study period using the Malmquist DEA-based productivity index. The productivity analysis is performed according to the year (period) and according to each studied seaport. The first output-oriented DEA method provides that the overall technical efficiency in the above-mentioned ports is 69.4% while the pure technical efficiency is 83.3%. Furthermore, the average scale efficiency is about 82.6%, which implies that the decreasing type of returns to scale dominates in this study. Regarding the second DEA application for productivity evolution, the obtained results from the data analysis revealed that it fell by 6.7%, mainly due to the degradation of the technological change (8.3%). The results obtained provide useful basic criteria for establishing efficiency improvement strategies for each studied seaport.

Does ramadan fasting affect the therapeutic and clinical outcomes of warfarin? a systematic review and meta-analysis - Eslam Mohammed Rabea; Kirellos Said Abbas; Dina M. Awad; Nancy H. Elgoweini; Amro Ahmed El-Sakka; Nada H. Mahmoud; Basel Abdelazeem (European Journal of Clinical Pharmacology, 2022)

Occupational ocular health problems among marble workers at Shaq El Tho’ban industrial area in Egypt - Enjy A. E. Khorshed; Safaa A. El-Naggar; Samia S. El-Gohary; Ahmed M. B. Awad; Amani S. Ahmed (Environmental Science and Pollution Research, 2022)
Eye health of the working population is an essential condition for productivity. Marble industry is processed at large scale at Shaq El Tho’ban area where much dust, crushed pieces of stone, and fluctuating temperatures are endangering employees’ health generally and eye health specifically. The objectives of this study were assessing the prevalence of the most common ocular health problems associated with marble industry and investigating the impact of the working environment and occupational risk factors on the oculo-visual status of marble workers. A cross-sectional study was conducted among 250 workers, working at Shaq El Tho’ban area in Egypt during the period from August 2020 to September 2021, using a semi-structured questionnaire and eye examination comprised of full ocular history, visual acuity testing (unaided/aided), slit lamp examination, ophthalmoscopy, and Schirmer’s type I and tear break up time tests. The current study showed that gritty sensation (65.2%) and eye dryness (51.2%) were the commonest symptoms complained. By examination, conjunctival hyperemia (59.6%) was the most prevalent finding. By performing dry eye tests, dry eye was diagnosed in 60.4% and 51.2% of workers by Schirmer’s test and tear break up time test respectively. The study’s results indicated that age, working category, smoking, and diabetes had significant impact on development of ocular symptoms, while working duration, diabetes, smoking, ocular symptoms, and ocular foreign body had significant impact on development of dry eye disease. Implementation of engineering control measures, proper designing, and supply of eye PPE together with adequate health education to all workers about occupational health risks and preventive measures are recommended.

Field and numerical studies to evaluate slope stability in municipal solid waste sites - M. F. Awad-Allah (Innovative Infrastructure Solutions, 2022)

Integrated Effect of Filter Mud Cake Combined with Chemical and Biofertilizers to Enhance Potato Growth and Its Yield - Ahmed M. Ali; Sabry A. Hegab; Assem M. Abd El Gawad; Mahrous Awad (Journal of Soil Science and Plant Nutrition, 2022)

Enhancement of photocatalytic and biological activities of chitosan/activated carbon incorporated with TiO2 nanoparticles - Medhat E. Owda; Ahmed S. Elfeky; Ragab E. Abouzeid; Ahmed K. Saleh; Mohamed A. Awad; Haitham A. Abdellatif; Fakher M. Ahmed; Ahmed S. Elzaref (Environmental Science and Pollution Research, 2022)

Seaport Terminals Risks Prioritization Using a Structural Modeling-Based Approach: A Real Case Study - Maryam Dhahri; Manel Elmsalmi; Awad M. Aljuaid; Wafik Hachicha (Journal of Marine Science and Engineering, 2022)
Port risk management (PRM) during port operations is a current problem that can negatively affect the environment, people, and economic issues. In the literature, there is an enormous amount of research related to supply chain risk management (SCRM) in various areas and with various objectives. However, PRM has not received the same degree of attention. In fact, port terminals are crucial links in most supply chain networks and an important pillar of international trade. Therefore, for better risk mitigation efficiency, a risk assessment and prioritization step are vital. Recently in the literature, researchers have applied prospective methods such as structural analysis methods to risk prioritization in SCRM. The aim of this research is to prioritize various man-made risk variables in PRM using a qualitative structural modeling-based approach, specifically, the MICMAC method (referring to its French acronym: Matrice d’Impacts Croisés Multiplication Appliquée à un Classement). An empirical study was conducted to assesses and prioritize risk variables of the seaport terminals of Sfax (Tunisia). The main contributions of the empirical research are twofold. First, to prioritize the key risk variables to define the most critical ones that require immediate intervention. Second, to analyze the structure of the influences between all identified risk variables. The results for the port terminals of Sfax show that the highest-priority risk variables are the manual handling (Ph3), disregard for safety aspects (Ph4), unsafe storage of goods (Inc1), absence of a prevention system and a rescue organization (Inc2), neglect of the regulatory aspects of handling equipment (M1), ignorance of good handling practices during the operation of loading and unloading (Cho2), and inadequate lifting accessories (Cho3). These risk variables must be the subject of urgent risk reduction strategies.

Verification of pull-out resistance of anchors in soil/rock formations using empirical and finite element methods - A. H. Abdel-Rahman; M. F. Awad-Allah (Innovative Infrastructure Solutions, 2022)

Therapeutic effect of dithiophenolato chitosan nanocomposites against carbon tetrachloride-induced hepatotoxicity in rats - Nadia Z. Shaban; Ahmed M. Aboelsaad; Doaa Awad; Shaymaa A. Abdulmalek; Shaban Y. Shaban (Environmental Science and Pollution Research, 2022)

Retraction Note to: Efficacy of favipiravir in COVID‑19 treatment: a multi‑center randomized study - Hany M. Dabbous; Sherief Abd‑Elsalam; Manal H. El‑Sayed; Ahmed F. Sherief; Fatma F. S. Ebeid; Mohamed Samir Abd El Ghafar; Shaimaa Soliman; Mohamed Elbahnasawy; Rehab Badawi; Mohamed Awad Tageldin (Archives of Virology, 2022)

Assessment of the Antibacterial Potential of Biosynthesized Silver Nanoparticles Combined with Vancomycin Against Methicillin-Resistant Staphylococcus aureus–Induced Infection in Rats - Mohammed Awad; Mohamed Yosri; Marwa M. Abdel-Aziz; Ahmed M. Younis; Nagwa M. Sidkey (Biological Trace Element Research, 2021)

Promising bioadhesive ofloxacin-loaded polymeric nanoparticles for the treatment of ocular inflammation: formulation and in vivo evaluation - Alaa H. Salama; Mona M. AbouSamra; Ghada E. A. Awad; Soheir S. Mansy (Drug Delivery and Translational Research, 2021)

An acetylated derivative of vitexin halts MDA-MB-231 cellular progression and improves its immunogenic profile through tuning miR- 20a-MICA/B axis - Aya R. Awad; Rana A. Youness; M. Ibrahim; Amira Abdel Motaal; Hesham I. El-Askary; Reem.A. Assal; Mohamed Z. Gad (Natural Product Research, 2021)

Evolutionary insights into the furin cleavage sites of SARS-CoV-2 variants from humans and animals - Abdou Nagy; Shereen Basiouni; Rokshana Parvin; Hafez M. Hafez; Awad A. Shehata (Archives of Virology, 2021)

Synoptic pattern of the Red Sea trough associated with spring dust over the northern and western Arabian Peninsula - Abdul-Wahab S. Mashat; Adel M. Awad; Mazen E. Assiri; Abdulhaleem H. Labban (Meteorology and Atmospheric Physics, 2021)

The First Report for the Presence of Spiroplasma and Rickettsia in Red Palm Weevil Rhynchophorus ferrugineus (Coleoptera: Curculionidae) in Egypt - Mona Awad; Abdoallah Sharaf; Tahany Abd Elrahman; Hassan Mohamed El-Saadany; Omnia Abdullah ElKraly; Sherif M. Elnagdy (Acta Parasitologica, 2021)

Embryonic thermal manipulation of Japanese quail: effects on embryonic development, hatchability, and post-hatch performance - Saad N. El-Shater; Hamdy Rizk; Hisham A. Abdelrahman; Mohamed A. Awad; Elsayed F. Khalifa; Karim M. Khalil (Tropical Animal Health and Production, 2021)

Brain Disease Network Analysis to Elucidate the Neurological Manifestations of COVID-19 - Kartikay Prasad; Suliman Yousef AlOmar; Saeed Awad M. Alqahtani; Md. Zubbair Malik; Vijay Kumar (Molecular Neurobiology, 2021)

Molecular docking studies, in-silico ADMET predictions and synthesis of novel PEGA-nucleosides as antimicrobial agents targeting class B1 metallo-β-lactamases - Jesica A. Mendoza; Richard Y. Pineda; Michelle Nguyen; Marisol Tellez; Ahmed M. Awad (In Silico Pharmacology, 2021)

RETRACTED ARTICLE: Efficacy of favipiravir in COVID-19 treatment: a multi-center randomized study - Hany M. Dabbous; Sherief Abd-Elsalam; Manal H. El-Sayed; Ahmed F. Sherief; Fatma F. S. Ebeid; Mohamed Samir Abd El Ghafar; Shaimaa Soliman; Mohamed Elbahnasawy; Rehab Badawi; Mohamed Awad Tageldin (Archives of Virology, 2021)

The variability of the Siberian high ridge over the Middle East - Abdulhaleem H. Labban; Abdul‐Wahab S. Mashat; Adel M. Awad (International Journal of Climatology, 2021)
An objective method was developed to detect local cells of the Siberian high (SH) over the Middle East, and mean sea level pressure (SLP) data from the National Centers for Environmental Prediction/National Center for Atmospheric Research reanalysis dataset were used to specify the centers of local SH cells and associated ridges. The results indicated that approximately 25.8% of winter SH cells influence the Middle East, and this influence diminishes from December to February. Synoptically, the area between the Black and Caspian Seas represents a remote area for sensing the influences of the SH on the Middle East. Although the SH is considered a shallow system, the variability of the effectiveness of the SH throughout the Middle East was estimated from the integration of atmospheric systems at the whole‐atmosphere scale (from the surface to 200 hPa). Further, this study demonstrated that the westward extension of the SH over the Middle East is associated with weak cyclogenesis in the area between the Black and Caspian Seas; that is, the atmospheric systems are favourable for strengthening the upper‐layer ridge in this area. However, the eastward retreat of the SH extension from the Middle East is associated with strong cyclogenesis in the area between the Black and Caspian Seas; that is, the atmospheric systems are unfavourable for strengthening the upper‐layer ridge in this area. This study revealed the importance of the SH in the generation of the pressure gradient over the Arabian Peninsula and the associated development of dust storms and the Red Sea Trough.

Synoptic features associated with the winter variability of the subtropical jet stream over Africa and the Middle East - Mana A. Asiri; Mansour Almazroui; Adel M. Awad (Meteorology and Atmospheric Physics, 2020)

Nano-diagnostic technique for detection of rice pathogenic fungus Pyricularia oryzae - Ibrahim H. El-Abbasi; Amal A. Khalil; Hossam M. Awad; Tahsin Shoala (Indian Phytopathology, 2020)

Molecular characterization of pathogenic Escherichia coli isolated from diarrheic and in-contact cattle and buffalo calves - Walid S. Awad; Amr A. El-Sayed; Faten F. Mohammed; Noha M. Bakry; Nadra-Elwgoud M. I. Abdou; Mohamed S. Kamel (Tropical Animal Health and Production, 2020)

Synoptic characteristics and ozone distributions associated with spring dust classes over the northern Arabian Peninsula - Abdul-Wahab S. Mashat; Ahmad O. Alamoudi; Adel M. Awad; Mazen E. Assiri (Arabian Journal of Geosciences, 2020)

Formulation and Evaluation of Novel Hybridized Nanovesicles for Enhancing Buccal Delivery of Ciclopirox Olamine - Mona M. AbouSamra; Alaa H. Salama; Ghada E. A. Awad; Soheir S. Mansy (AAPS PharmSciTech, 2020)

Effect of a Dietary Mixture of Beneficial Bacteria on Growth Performance, Health Condition, Chemical Composition, and Water Quality of Nile Tilapia, Oreochromis niloticus Fingerlings - Malik M. Khalafalla; Safinaz A. Ibrahim; Mohamed M. Zayed; Mohamed N. Awad; Radi A. Mohamed (Journal of Aquatic Food Product Technology, 2020)

Repurposing of Secukinumab as Neuroprotective in Cuprizone-Induced Multiple Sclerosis Experimental Model via Inhibition of Oxidative, Inflammatory, and Neurodegenerative Signaling - Amany El-Shahawy Abdel-Maged; Amany M. Gad; Laila Ahmed Rashed; Samar S. Azab; Eman A. Mohamed; Azza S. Awad (Molecular Neurobiology, 2020)

Protective potency of Astragalus polysaccharides against tilmicosin- induced cardiac injury via targeting oxidative stress and cell apoptosis-encoding pathways in rat - Ashraf Awad; Samah R. Khalil; Basma M. Hendam; Reda M. Abd El-Aziz; Mohamed M. M. Metwally; Tamer S. Imam (Environmental Science and Pollution Research, 2020)

Correction to: Indoor air fungal pollution of a historical museum, Egypt: a case study - Abdel Hameed A. Awad; Yuosra Saeed; Alia A. Shakour; Nasser M. Abdellatif; Yasser H. Ibrahim; Manal Elghanam; Fatma Elwakeel (Aerobiologia, 2020)

Indoor air fungal pollution of a historical museum, Egypt: a case study - Abdel Hameed A. Awad; Yuosra Saeed; Alia A. Shakour; Nasser M. Abdellatif; Yasser H. Ibrahim; Manal Elghanam; Fatma Elwakeel (Aerobiologia, 2020)

Dynamic and synoptic study of spring dust storms over northern Saudi Arabia - Abdul-Wahab S. Mashat; Adel M. Awad; Mazen E. Assiri; Abdulhaleem H. Labban (Theoretical and Applied Climatology, 2020)

Monthly and seasonal variability of dust events over northern Saudi Arabia - Abdul‐Wahab S. Mashat; Adel M. Awad; Ahmad O. Alamoudi; Mazen E. Assiri (International Journal of Climatology, 2020)
The monthly and seasonal variability and distribution of dust events over northern Saudi Arabia were studied using ground‐based measurements from 11 surface stations for the period of 1978–2010. Additionally, to study the synoptic climatology of the dust variability, the aerosol index (AI) data from the Total Ozone Mapping Spectrometer (TOMS) satellite and meteorological data from the National Center for Environmental Prediction and National Center for Atmospheric Research (NCEP/NCAR) reanalysis datasets were used. The dust types observed at the surface stations are classified into two categories: weak dust and dust storms. A statistical study of the ground measurements demonstrated that weak dust category events are prevalent in the cold months, whereas storm category events are prevalent in the hot months. Additionally, the annual distribution distinguishes two periods for dust observations, before and after 1989, where the number of events in the first period is lower than the annual average but increases during the second period. The synoptic climate study indicated that two main atmospheric wind patterns, anticyclonic and northerly (shamal) patterns, accompany the dust events in the study area. The dust in winter and autumn is mainly affected by the anticyclonic pattern, while that in spring and summer is mainly affected by the shamal pattern. In addition, a synoptic study of selected cases confirmed the climate results and demonstrated the existence of two atmospheric patterns corresponding to winter and summer. Both patterns include troughs over the Red Sea and Arabian Gulf and a ridge or high‐pressure cell over the eastern Mediterranean region during the summer atmospheric pattern and over the mid‐Arabian Peninsula during the winter atmospheric pattern. The characteristic of non‐dust storm composition demonstrated that the storms exhibit pronounced synoptic systems (winter and summer) with the highest pressure/geopotential gradient near the Arabian Peninsula.

Main atmospheric regimes of the long winter Red Sea trough - Abdulhaleem H. Labban; Abdul-Wahab S. Mashat; Adel M. Awad (Arabian Journal of Geosciences, 2020)

Effect of dietary purslane (Portulaca oleracea L.) leaves powder on growth, immunostimulation, and protection of Nile tilapia, Oreochromis niloticus against Aeromonas hydrophila infection - Nashwa Abdel-Razek; Somayah M. Awad; Mohsen Abdel-Tawwab (Fish Physiology and Biochemistry, 2019)

Exogenous application of β-sitosterol mediated growth and yield improvement in water-stressed wheat (Triticum aestivum) involves up-regulated antioxidant system - Amr Elkeilsh; Yasser M. Awad; Mona H. Soliman; Abdelghafar Abu-Elsaoud; Magdi T. Abdelhamid; Ibrahim M. El-Metwally (Journal of Plant Research, 2019)

Neutron activation and ICP-MS analyses of metals in dust samples—Kingdom of Saudi Arabia: concentrations, pollution, and exposure - Atef El-Taher; Wael M. Badawy; B. Alshahrani; Awad A. Ibraheem (Arabian Journal of Geosciences, 2019)

Effects of Dietary Supplementation of Probiotic Mix and Prebiotic on Growth Performance, Cecal Microbiota Composition, and Protection Against Escherichia coli O78 in Broiler Chickens - Reda Tarabees; Khaled M. Gafar; Mohamed S. EL-Sayed; Awad A. Shehata; Marwa Ahmed (Probiotics and Antimicrobial Proteins, 2019)

Climatology of the spring Red Sea Trough - Muhammad N. Baseer; Adel M. Awad; Mansour Almazroui (International Journal of Climatology, 2019)
The spring Sudan low and its Red Sea Trough (RST) were detected objectively using sea level pressure data obtained from a National Center for Environmental Prediction/National Center for Atmospheric Research reanalysis dataset spanning the period from 1955 to 2014. The climatology of the detected lows suggested that the Sudan low was active for approximately 69.5% of the spring and that approximately 56.2% of this time the Sudan low developed into the RST. Furthermore, three main genesis regions of the RST, which generated 95.25% of the RST, were identified over Sudan, South Sudan and the Red Sea, approximately 61.76% of which was over South Sudan. In addition, three main outermost areas of the RST, which received 94.1% of the RST, were specified to the west, east and north of the Red Sea, approximately 54.88% of which was in the eastern region. Synoptically, the orientations of the detected RST around the Red Sea are strongly influenced by the Siberian and Azores high systems. The RST is directed along the western side of the Red Sea if the Siberian high extends westward and the Azores high shrinks westward, whereas the RST is oriented to the east if the Siberian high shrinks eastward and the Azores high extends eastward. The RST extends directly northward if the Siberian and Azores high systems withdraw eastward and westward, respectively. These results also demonstrate that the core position and strength of the upper maximum winds play an important role in the generation of RST. The selected case studies have confirmed the synoptic climate results and indicate that the Sudan low will not develop into RST when the northern region has been affected by a high‐pressure system and the core of the upper maximum wind is located over the northern Arabian Peninsula.

Endophytic actinomycetes Streptomyces spp mediated biosynthesis of copper oxide nanoparticles as a promising tool for biotechnological applications - Saad El-Din Hassan; Amr Fouda; Ahmed A. Radwan; Salem S. Salem; Mohammed G. Barghoth; Mohamed A. Awad; Abdullah M. Abdo; Mamdouh S. El-Gamal (JBIC Journal of Biological Inorganic Chemistry, 2019)

Involvement of Nrf2/HO-1 antioxidant signaling and NF-κB inflammatory response in the potential protective effects of vincamine against methotrexate-induced nephrotoxicity in rats: cross talk between nephrotoxicity and neurotoxicity - Youssef M. Shalaby; Esther T. Menze; Samar S. Azab; Azza S. Awad (Archives of Toxicology, 2019)

Climatology of the autumn Red Sea trough - Adel M. Awad; Abdul-Wahab S. Mashat (Theoretical and Applied Climatology, 2019)

The Utilization of Electric Arc Furance Slag in Soil Improvement - A. I. M. Ismail; S. A. Awad; M. A. G. Mwafy (Geotechnical and Geological Engineering, 2019)

Effect of water injection into the intake manifold on combustion and NOx emissions of CHP engine fuelled with natural gas - Omar I. Awad; H. Arruga; Hai Tao; F. Scholl; M. Kettner; M. Klaissle; Rizalman Mamat (Clean Technologies and Environmental Policy, 2019)

Empagliflozin, SGLT2 inhibitor, attenuates renal fibrosis in rats exposed to unilateral ureteric obstruction: potential role of klotho expression - Noha A. T. Abbas; Amal El. Salem; Mohammed M. Awad (Naunyn-Schmiedeberg's Archives of Pharmacology, 2018)

Association between exposure to pesticides and disorder on hematological parameters and kidney function in male agricultural workers - Nagah M. Hassanin; Osama M. Awad; Sourya El-Fiki; Reda A. I. Abou-Shanab; Ahmed R. A. Abou-Shanab; Ranya A. Amer (Environmental Science and Pollution Research, 2018)

Characteristics of the internal and external sources of the Mediterranean synoptic cyclones for the period 1956–2013 - Mansour Almazroui; Adel M. Awad; M. Nazrul Islam (Theoretical and Applied Climatology, 2018)

Peg-manipulation capabilities of middle-aged adults have a greater influence on pegboard times than those of young and old adults - Awad M. Almuklass; Daniel F. Feeney; Diba Mani; Landon D. Hamilton; Roger M. Enoka (Experimental Brain Research, 2018)

PCB dechlorination hotspots and reductive dehalogenase genes in sediments from a contaminated wastewater lagoon - Timothy E. Mattes; Jessica M. Ewald; Yi Liang; Andres Martinez; Andrew Awad; Patrick Richards; Keri C. Hornbuckle; Jerald L. Schnoor (Environmental Science and Pollution Research, 2018)

Formulation and characterization of garlic (Allium sativum L.) essential oil nanoemulsion and its acaricidal activity on eriophyid olive mites (Acari: Eriophyidae) - Abdel-Tawab H. Mossa; Sahar I. Afia; Samia M. M. Mohafrash; Badawi A. Abou-Awad (Environmental Science and Pollution Research, 2018)

Quercetin Reverses Altered Energy Metabolism in the Heart of Rats Receiving Adriamycin Chemotherapy - Naglaa Zakaria; Samah R. Khalil; Ashraf Awad; Ghada M. Khairy (Cardiovascular Toxicology, 2018)

Flavones from Heavenly Blue as modulators of Alzheimer’s amyloid-beta peptide (Aβ) production - Hanem M. Awad; Howaida I. Abd-Alla; Mohamed A. Ibrahim; Eslam R. El-Sawy; Mohamed M. Abdalla (Medicinal Chemistry Research, 2018)

Synthesis and in vitro antitumor evaluation of novel Schiff bases - Ashraf S. Hassan; Hanem M. Awad; Asmaa A. Magd-El-Din; Taghrid S. Hafez (Medicinal Chemistry Research, 2018)

The use of connectivity clusters in stochastic modelling of highly heterogeneous porous media - Mohamed A. Awad; Ahmed E. Hassan; Hesham M. Bekhit (Arabian Journal of Geosciences, 2018)

Seasonal variability and synoptic characteristics of dust cases over southwestern Saudi Arabia - Abdul‐Wahab S. Mashat; Ahmad O. Alamoudi; Adel M. Awad; Mazen E. Assiri (International Journal of Climatology, 2018)
The synoptic characteristics and statistical variability of seasonal dust over southwestern Saudi Arabia are studied for the period from 1979 to 2006 using the aerosol index ( AI ) from the Total Ozone Mapping Spectrometer ( TOMS ) satellite, dust observations from surface stations, and meteorological data from the National Center for Environmental Prediction and the National Center for Atmospheric Research ( NCEP / NCAR ) reanalysis data set. The seasonal AI distribution indicates that approximately 80% of each year was dusty and that most of the dust occurred during hot months. In addition, the surface observations of the dust types show that the stations with the largest number of dust observations throughout the year were close to the desert, except during the summer, when the stations near the Red Sea had the largest number of dust observations. The synoptic forces that influenced the dust cases were the relative positions of high‐pressure systems (Azores or Siberian) and low‐pressure systems (Sudan or Indian), alongside their interactions. The relative positions of the atmospheric systems are highly pronounced at a pressure level of 850 hPa ; at this pressure, the systems are oriented from north (anticyclonic system) to south (cyclonic system), turn anticlockwise to become oriented from west (anticyclonic system) to east (cyclonic system) during the summer, and then turn clockwise during the winter. Moreover, the interaction of the atmospheric systems influences the wind pattern of the seasonal composition over the southern Arabian Peninsula, which produces an anticyclonic wind pattern during winter, a cyclonic wind pattern during spring, a northerly/northwesterly wind pattern during summer and an anticyclonic wind pattern during autumn. The dust sources changed because of the relative positions of these atmospheric systems, in which the ‘Toker Gap’ Sudan was the summer/autumn dust source, and the ‘central and eastern’ Arabian Peninsula was the winter/spring dust source.

Peg-manipulation capabilities during a test of manual dexterity differ for persons with multiple sclerosis and healthy individuals - Awad M. Almuklass; Daniel F. Feeney; Diba Mani; Landon D. Hamilton; Roger M. Enoka (Experimental Brain Research, 2017)

Neuroprotective Effects of Simvastatin and Cilostazol in l-Methionine-Induced Vascular Dementia in Rats - Ahmed M. El-Dessouki; Mai A. Galal; Azza S. Awad; Hala F. Zaki (Molecular Neurobiology, 2017)

Cytotoxic activity evaluation and molecular docking study of phenolic derivatives from Achillea fragrantissima (Forssk.) growing in Egypt - Basma M. Awad; Eman S. Habib; Amany K. Ibrahim; Amira S. Wanas; Mohamed M. Radwan; Mohamed A. Helal; Mahmoud A. ElSohly; Safwat A. Ahmed (Medicinal Chemistry Research, 2017)

Control of force during rapid visuomotor force-matching tasks can be described by discrete time PID control algorithms - Jakob Lund Dideriksen; Daniel F. Feeney; Awad M. Almuklass; Roger M. Enoka (Experimental Brain Research, 2017)

Impact of thyme powder (Thymus vulgaris L.) supplementation on gene expression profiles of cytokines and economic efficiency of broiler diets - Fardos A. M. Hassan; Ashraf Awad (Environmental Science and Pollution Research, 2017)

Possible correlation between levansucrase production and probiotic activity of Bacillus sp. isolated from honey and honey bee - Abdelhamid A. Hamdy; Nouran A. Elattal; Magdy A. Amin; Amal E. Ali; Nahla M. Mansour; Ghada E. A. Awad; Hassan M. Awad; Mona A. Esawy (World Journal of Microbiology and Biotechnology, 2017)

Synoptic characteristics of dusty spring days over central and eastern Saudi Arabia - Abdul-Wahab S. Mashat; Ahmad O. Alamoudi; Adel M. Awad; Mazen E. Assiri (Air Quality, Atmosphere & Health, 2017)

Efficacy of cold fogging and oral herbal extracts on air quality and immune response of broilers - Awad A. Shehata; Klaus Herrmann; Thomas Pfalz; Hafez M. Hafez; Wieland Schrödl; Monika Krüger (Aerobiologia, 2017)

Using Supercritical Fluid Technology (SFT) in Preparation of Tacrolimus Solid Dispersions - Rana M. Obaidat; Bassam M. Tashtoush; Alaa Abu Awad; Rana T. Al Bustami (AAPS PharmSciTech, 2017)

3D Printing of Calcium Phosphate Ceramics for Bone Tissue Engineering and Drug Delivery - Ryan Trombetta; Jason A. Inzana; Edward M. Schwarz; Stephen L. Kates; Hani A. Awad (Annals of Biomedical Engineering, 2017)

Effect of Water Regimes and Palm Coefficient on Growth Parameters, Date Yield and Irrigation Water Use of Tissue Culture‐Regenerated ‘Barhee’ Date Palms Grown in a Newly Established Orchard - Adel D. Al‐Qurashi; Saleh M. Ismail; Mohamed A. Awad (Irrigation and Drainage, 2016)
A field experiment was carried out at the Agriculture Experimental Station of King Abdulaziz University during the 2013 and 2014 seasons to study the effect of water regimes and palm coefficient on growth parameters, yield and irrigation water use (IWU) of tissue culture‐derived ‘Barhee’ date palm cultivars in a newly established orchard. Four water regimes T1, T2, T3 and T4 representing 70, 85, 100 and 115% of water requirement were studied to select the best water regime that maximizes yield and IWU. Water requirement in 2013 was calculated based on the FAO palm coefficient ( K p ) but based on measured K p during 2014. Results revealed that using measured K p reduces water requirements in the summer season and increases date yield. It saves about 12% of irrigation water compared to FAO K p . Increasing the water regime increased yield per palm, where the highest yield was obtained from T4 (16.5 kg per tree), and the least from T1(12.4 kg per tree). IWU is increased by decreasing the water regime. However, the differences between T4 and T3 were not significant, indicating that giving the highest water regime produces the highest yield. It is concluded that increasing water supply maximizes yield production of young tissue culture‐derived ‘Barhee’ date palms in a newly established orchard. Copyright © 2016 John Wiley & Sons, Ltd.

Two new proanthocyanidin trimers isolated from Cistus incanus L. demonstrate potent anti-inflammatory activity and selectivity to cyclooxygenase isoenzymes inhibition - K. A. Mansoor; K. Z. Matalka; F. S. Qa’dan; R. Awad; M. Schmidt (Natural Product Research, 2016)

Anticancer activity of some [1,2,4]triazepino[2,3-a] quinazoline derivatives: monolayer and multicellular spheroids in vitro models - Hanem M. Awad; Walid Fayad; Salwa M. El-Hallouty; Thoraya A. Farghaly; Mohamad M. Abdallah (Medicinal Chemistry Research, 2016)

Synoptic study of the seasonal variability of dust cases observed by the TOMS satellite over northern Saudi Arabia - Adel M. Awad; Abdul-Wahab S. Mashat; Ahmad O. Alamoudi; Mazen E. Assiri (Theoretical and Applied Climatology, 2016)

Thymoquinone alleviates nonalcoholic fatty liver disease in rats via suppression of oxidative stress, inflammation, apoptosis - Azza S. M. Awad; Ekram N. Abd Al Haleem; Wesam M. El-Bakly; Mohie A. Sherief (Naunyn-Schmiedeberg's Archives of Pharmacology, 2016)

Source mechanism and parameters of the 19 October 2012 earthquake, northern Egyptian continental margin - Awad Hassoup; Mostafa Toni; M. M. F. Shokry; A. M. A. Helal; Emad K. Mohamed (Arabian Journal of Geosciences, 2016)

Synoptic characteristics of spring dust days over northern Saudi Arabia - Adel M. Awad; Abdul-Wahab S. Mashat (Air Quality, Atmosphere & Health, 2016)

Curcumin Ameliorates Lead (Pb2+)-Induced Hemato-Biochemical Alterations and Renal Oxidative Damage in a Rat Model - Ashraf M. Abdel-Moneim; Mona Y. El-Toweissy; Awatef M. Ali; Abd Allah M. Awad Allah; Hanaa S. Darwish; Ismail A. Sadek (Biological Trace Element Research, 2015)

Unbalanced polyandry in wild-caught ladybirds Harmonia axyridis (Coleoptera: Coccinellidae) - Mona Awad; Guillaume J. M. Laugier; Anne Loiseau; Oldřich Nedvěd (Applied Entomology and Zoology, 2015)

Delineating subsurface structures and assessment of groundwater aquifer using integrated geophysical interpretation at the central part of Sinai, Egypt - Sultan Awad Sultan Araffa; Hassan M. El Shayeb; Mohamed F. Abu Hashesh; Noha M. Hassan (Arabian Journal of Geosciences, 2015)

A climatological study: wet season cyclone tracks in the East Mediterranean region - Mansour Almazroui; Adel M. Awad; M. Nazrul Islam; A. K. Al-Khalaf (Theoretical and Applied Climatology, 2015)

Diagnostic study of spring dusty days over the southwest region of the Kingdom of Saudi Arabia - Adel M. Awad; Abdul-Wahab S. Mashat; Faisal F. Abo Salem (Arabian Journal of Geosciences, 2015)

In vitro anti-nitrosative, antioxidant, and cytotoxicity activities of plant flavonoids: a comparative study - Hanem M. Awad; Howaida I. Abd-Alla; Khaled H. Mahmoud; Sayed A. El-Toumy (Medicinal Chemistry Research, 2014)

Synoptic features associated with dust transition processes from North Africa to Asia - Adel M. Awad; Abdul-Wahab S. Mashat (Arabian Journal of Geosciences, 2014)

Log-derived petrophysical characteristics and oil potentiality of the Upper Qishn Clastic Member, Masila Basin, Yemen - Awad A. Omran; Nabil M. Alareeq (Arabian Journal of Geosciences, 2014)

Life history traits of Blaptostethus pallescens (Hemiptera: Anthocoridae), a candidate for use in augmentative biological control in Egypt - Islam S. Sobhy; Amany M. Abdul-Hamid; Awad A. Sarhan; Ahmed A. Shoukry; Nasser S. Mandour; Stuart R. Reitz (Applied Entomology and Zoology, 2014)

Life history of Proprioseiopsis badri feeding on four eriophyid mite species (Acari: Phytoseiidae and Eriophyidae) - Faten M. Momen; Abd-Elsatar M. Metwally; Abd Elrady K. Nasr; Awad A. Abdallah; Khaled M. Saleh (Phytoparasitica, 2014)

OPTIMIZATION OF IRRIGATION WATER USE, YIELD, AND QUALITY OF 'NABBUT‐SAIF' DATE PALM UNDER DRY LAND CONDITIONS - Saleh M. Ismail; Adel D. Al‐Qurashi; Mohamed A. Awad (Irrigation and Drainage, 2014)
A field experiment was conducted in the western part of Saudi Arabia to optimize irrigation water use (IWU), yields and quality of the 'Nabbut‐Saif' date palm grown in sandy loam soil under arid conditions. Four water regimes were investigated. The supplied amounts of irrigation water were 50, 65, 82 and 100% of date palm water requirements to the first (W1), second (W2), third (W3) and fourth (W4) water regimes, respectively. The daily water requirement was calculated using the Penman–Montieth equation for dry climates and applied to the trees three times a week through a drip irrigation system. Results indicated that giving 65% of total date palm water requirement maximized date yield by producing 46.1 kg per tree and resulted in the best IWU (0.8 m 3 kg −1 per tree). Increasing the water regime to 82 and 100% of total water requirement produced only 45.5 and 46 kg per tree respectively and reduced IWU. Generally, fruit quality characteristics were insignificantly affected by the water regimes investigated. The results suggested that supplying 34 m 3 yr −1 per tree for date palms grown under the conditions of the western part of Saudi Arabia is enough to maximize IWU, yield and quality of the 'Nabbut‐Saif' date palm cultivar. Copyright © 2014 John Wiley & Sons, Ltd.

The Effect of Glyphosate on Potential Pathogens and Beneficial Members of Poultry Microbiota In Vitro - Awad A. Shehata; Wieland Schrödl; Alaa. A. Aldin; Hafez M. Hafez; Monika Krüger (Current Microbiology, 2013)

Design, synthesis, anti-inflammatory, analgesic screening, and molecular docking of some novel 2-pyridyl (3H)-quinazolin-4-one derivatives - Ahmad F. Eweas; Ahmed O. H. El-Nezhawy; Ayman R. Baiuomy; Mohamed M. Awad (Medicinal Chemistry Research, 2013)

Exploration of copper deposits in Wadi El Regeita area, Southern Sinai, Egypt, with contribution of remote sensing and geophysical data - S. M. Salem; Sultan Awad Arafa; T. M. Ramadan; El Sayed A. El Gammal (Arabian Journal of Geosciences, 2013)

Regional Heterogeneity of Cuprizone-Induced Demyelination: Topographical Aspects of the Midline of the Corpus Callosum - T. Schmidt; H. Awad; A. Slowik; C. Beyer; M. Kipp; T. Clarner (Journal of Molecular Neuroscience, 2013)

Lateral variations of coda Q and attenuation of seismic waves in the Gulf of Suez, Egypt - Mamdouh A. Morsy; Sherif El Hady; Salah M. Mahmoud; Enayat Abdel Moneim Awad (Arabian Journal of Geosciences, 2013)

Association study between the dopamine-related candidate gene polymorphisms and ADHD among Saudi Arabia population via PCR technique - Adel E. El-Tarras; Adnan A. Alsulaimani; Nabil S. Awad; Nahla Mitwaly; Manal M. Said; Ayman M. Sabry (Molecular Biology Reports, 2012)

Effect of some pyrimidine compounds on rat brain monoamine oxidase-B in vitro - Nadia Z. Shaban; Mamdouh S. Masoud; Mai A. Mawlawi; Doaa Awad; Omayma M. Sadek (Journal of Physiology and Biochemistry, 2012)

A new geometric model for clustering high-resolution satellite images - M. M. Awad (International Journal of Remote Sensing, 2012)

Inflammatory Response and Chemokine Expression in the White Matter Corpus Callosum and Gray Matter Cortex Region During Cuprizone-Induced Demyelination - J. P. Buschmann; K. Berger; H. Awad; T. Clarner; C. Beyer; M. Kipp (Journal of Molecular Neuroscience, 2012)

Efficacy of Ficus spp. on renal injury induced by hypercholesterolaemia - Nagwa E. Awad; Manal A. Hamed; Ahmed A. Seida; Marwa M. Elbatanony (Natural Product Research, 2012)

Phytochemical and in vitro screening of some Ficus and Morus spp. for hypolipidaemic and antioxidant activities and in vivo assessment of Ficus mysorensis (Roth) - Nagwa E. Awad; Ahmed A. Seida; Manal A. Hamed; Ahlam H. Mahmoud; Marwa M. Elbatanony (Natural Product Research, 2012)

Fluorescence and Electrochemical Recognition of Nucleosides and DNA by A Novel Luminescent Bioprobe Eu(lll) -TNB - Hassan A. Azab; E. M. Mogahed; F. K. Awad; R. M. Abd El Aal; Rasha M. Kamel (Journal of Fluorescence, 2012)

Less is More: Treatment with BTH and Laminarin Reduces Herbivore-Induced Volatile Emissions in Maize but Increases Parasitoid Attraction - Islam S. Sobhy; Matthias Erb; Awad A. Sarhan; Monir M. El-Husseini; Nasser S. Mandour; Ted C. J. Turlings (Journal of Chemical Ecology, 2012)

Fluorescence and Electrochemical Sensing of Pesticides Methomyl, Aldicarb and Prometryne by the Luminescent Europium-3-Carboxycoumarin Probe - Hassan A. Azab; Axel Duerkop; E. M. Mogahed; F. K. Awad; R. M. Abd El Aal; Rasha M. Kamel (Journal of Fluorescence, 2012)

Endogenous tissue engineering: PTH therapy for skeletal repair - Masahiko Takahata; Hani A. Awad; Regis J. O’Keefe; Susan V. Bukata; Edward M. Schwarz (Cell and Tissue Research, 2012)

Integrated geophysical interpretation for the area located at the eastern part of Ismailia Canal, Greater Cairo, Egypt - Sultan Awad Sultan; Fernando A. M. Santos; Ahmad Sobhy Helaly (Arabian Journal of Geosciences, 2011)

Hypolipidaemic and antioxidant activities of Ficus microcarpa (L.) in hypercholesterolemic rats - Nagwa E. Awad; Ahmed A. Seida; Manal A. Hamed; Marwa M. Elbatanony (Natural Product Research, 2011)

Broad‐scale latitudinal patterns of genetic diversity among native European and introduced house sparrow ( Passer domesticus ) populations - A. W. SCHREY; M. GRISPO; M. AWAD; M. B. COOK; E. D. McCOY; H. R. MUSHINSKY; T. ALBAYRAK; S. BENSCH; T. BURKE; L. K. BUTLER; R. DOR; H. B. FOKIDIS; et al. (Molecular Ecology, 2011)
Introduced species offer unique opportunities to study evolution in new environments, and some provide opportunities for understanding the mechanisms underlying macroecological patterns. We sought to determine how introduction history impacted genetic diversity and differentiation of the house sparrow ( Passer domesticus ), one of the most broadly distributed bird species. We screened eight microsatellite loci in 316 individuals from 16 locations in the native and introduced ranges. Significant population structure occurred between native than introduced house sparrows. Introduced house sparrows were distinguished into one North American group and a highly differentiated Kenyan group. Genetic differentiation estimates identified a high magnitude of differentiation between Kenya and all other populations, but demonstrated that European and North American samples were differentiated too. Our results support previous claims that introduced North American populations likely had few source populations, and indicate house sparrows established populations after introduction. Genetic diversity also differed among native, introduced North American, and Kenyan populations with Kenyan birds being least diverse. In some cases, house sparrow populations appeared to maintain or recover genetic diversity relatively rapidly after range expansion (

Air biocontamination in a variety of agricultural industry environments in Egypt: a pilot study - Abdel Hameed A. Awad; Tarek H. Elmorsy; Patrick M. Tarwater; Christopher F. Green; Shawn G. Gibbs (Aerobiologia, 2010)

Evaluation of different diagnostic methods for diagnosis of Lumpy skin disease in cows - Walid S. Awad; Adel K. Ibrahim; Khaled Mahran; Khaled M. Fararh; Mervet I. Abdel Moniem (Tropical Animal Health and Production, 2010)

Hydrogeophysical study of the El Qaa Plain, Sinai, Egypt - Sultan Awad Sultan; Mahmoud Ismail Mohameden; Fernando M. Santos (Bulletin of Engineering Geology and the Environment, 2009)

Groundwater exploration and evaluation by using geophysical interpretation (case study: Al Qantara East, North Western Sinai, Egypt) - Sultan Awad Sultan; Hatem M. Mekhemer; Fernando M. Santos (Arabian Journal of Geosciences, 2009)

Multicomponent image segmentation: a comparative analysis between a hybrid genetic algorithm and self‐organizing maps - M. M. Awad; K. Chehdi; A. Nasri (International Journal of Remote Sensing, 2009)

Release Mechanisms Behind Polysaccharides-Based Famotidine Controlled Release Matrix Tablets - Enas M. Elmowafy; Gehanne A. S. Awad; Samar Mansour; Abd El-Hamid A. El-Shamy (AAPS PharmSciTech, 2008)

A new systematic approach for water network design - S. Aly; S. Abeer; M. Awad (Clean Technologies and Environmental Policy, 2005)

In vitro propagation and cryostorage of Syzygium francissi (Myrtaceae) by the encapsulation-dehydration method - M. Awad Shatnawi; Krystyna A. Johnson; Fraser R. Torpy (In Vitro Cellular & Developmental Biology - Plant, 2004)

Blastocystis hominis as a cause of hypoalbuminemia and anasarca - E. Nassir; J. Awad; A. B. Abel; J. Khoury; M. Shay; F. Lejbkowicz (European Journal of Clinical Microbiology & Infectious Diseases, 2004)

Modulation of mitogen-independent hepatocyte proliferation during the perinatal period in the rat - Philip A. Gruppuso; Michael Awad; Theresa C. Bienieki; Joan M. Boylan; Shaneli Fernando; Ronald A. Faris (In Vitro Cellular & Developmental Biology - Animal, 1997)

Biological studies ofAmblyseius olivi, a new predator of eriophyid mites infesting olive trees in Egypt [Acari: Phytoseiidae] - B. A. Abou-Awad; E. M. El-Banhawy (BioControl, 1986)

Effect of synthetic pyrethroids and other compounds on the susceptibility and development of the egg stage of the predacious miteAmblyseius gossipi [Mesostigmata: Phytoseiidae] - E. M. El-Banhawy; B. A. Abou-Awad (BioControl, 1985)